Separator for power storage device and power storage device comprising same

By using polyolefin microporous membrane substrate and inorganic filler with thermoplastic granular polymer in the separator of energy storage equipment, the problems of uneven adhesion and poor heat resistance are solved, improving battery productivity and battery performance, especially battery output and cycle characteristics in high-density modularization.

CN119278539APending Publication Date: 2025-01-07ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380042862.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-27
Filing Date
2023-05-26
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing separators for energy storage devices suffer from problems such as uneven adhesion, poor heat resistance, low productivity, and insufficient battery output and cycle characteristics, which are particularly prominent in the process of high-density modularization.

Method used

The separator design incorporates a polyolefin microporous membrane as the substrate and a cover layer. The cover layer is composed of inorganic fillers and thermoplastic granular polymer. The static friction coefficient of the cover layer is above 0.40 and below 0.60. The area ratio of the protruding part of the granular polymer is below 10%. The tilt rate and coverage are within a specific range to ensure good adhesion and heat resistance to the electrode.

Benefits of technology

It improves the adhesion between the separator and the electrode, suppresses thermal shrinkage, and enhances battery productivity and performance, including improved rate performance and cycle performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278539A_ABST
    Figure CN119278539A_ABST
Patent Text Reader

Abstract

Provided is a separator for an electricity storage device, the separator comprising a base material (10), which is a polyolefin microporous film containing a polyolefin as a main component, and a cover layer (20), which is disposed on at least one surface of the base material (10) and contains an inorganic filler (1) and a thermoplastic polymer, the thermoplastic polymer constitutes a particulate polymer (2) protruding from the inorganic filler portion (L1), and the coating layer (20) has a static friction coefficient of 0.40-0.60.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a separator for an electric storage device and an electric storage device including the separator. Background Art

[0002] The development of power storage devices represented by lithium-ion secondary batteries is being actively carried out. Generally speaking, power storage devices include a positive electrode and a negative electrode, and a separator including a microporous membrane between them. The separator has the function of preventing the positive electrode from directly contacting the negative electrode and allowing ions to pass through the electrolyte retained in the micropores. The separator is required to have safety properties such as the property of quickly stopping the battery reaction in the event of abnormal heating (fusing property), and the property of maintaining the shape even at high temperatures to prevent the dangerous situation of direct reaction between the positive electrode and the negative electrode (short circuit resistance property).

[0003] Non-aqueous secondary batteries such as lithium-ion secondary batteries are put on the market in various shapes such as cylindrical, square, and pouch types according to their uses. The manufacturing method of the battery varies depending on the shape of the battery. For example, the manufacturing method of a square battery has the following steps: a laminate of an electrode and a separator, or a wound body formed by winding a laminate of an electrode and a separator, is pressurized and inserted into a rectangular outer can.

[0004] In recent years, in order to increase the capacity of power storage devices, the following operations have been carried out: the volume of power storage devices is reduced by hot pressing a stack of electrodes and separators, or hot pressing a wound body formed by winding a stack of electrodes and separators. At this time, the following technology is known: in order to fix the electrodes and separators after hot pressing and maintain the volume during pressing, a covering layer containing a thermoplastic polymer that exhibits an adhesive function under predetermined conditions is arranged on a substrate, thereby improving the adhesion between the separator as a whole and the electrode.

[0005] Patent Document 1 describes a separator having a porous coating layer containing organic polymer particles in order to improve the bonding strength between the separator and the electrode and enhance safety even without performing a humidification phase separation process of an organic binder polymer and a secondary coating process of an adhesive layer. In the separator, the organic polymer particles protrude from the surface of the porous coating layer by a height of 0.1 μm or more and 3 μm or less.

[0006] Patent Document 2 describes a separator having a functional layer including inorganic particles and a granular polymer in order to provide a separator having excellent adhesion and heat resistance and improved electrolyte injection properties. When the surface of the functional layer is viewed from above, the area ratio of the inorganic particles per unit area of ​​the functional layer exceeds 90%, the volume average particle size of the granular polymer is within a specific range, and the volume average particle size of the granular polymer is greater than the thickness of the inorganic particle layer.

[0007] Patent document 3 describes a separator having a functional layer including inorganic particles and a granular polymer in order to provide an electrochemical element functional layer with excellent process adhesion and excellent cycle characteristics. The functional layer has a particle shedding portion, and when the surface of the electrochemical element functional layer is viewed from above, the area of ​​the particle shedding portion accounts for a proportion of 0.1% or more and 40.0% or less in the total area of ​​the granular polymer and the particle shedding portion, and the volume average particle size of the granular polymer is greater than the thickness of the inorganic particle layer including the inorganic particles.

[0008] In patent document 4, focusing on the lamination, insulation, curling, adhesion to electrodes and use of polyvinylidene fluoride (PVDF) of separators for non-aqueous secondary batteries, and the cycle characteristics of non-aqueous secondary batteries, for a laminate having a porous layer containing a resin on at least one surface of a porous film containing polyolefin as the main component, the relationship between the critical surface tension of the outermost surface of the porous layer and the critical surface tension of the interface side of the porous film, or the increase in the amount of insulation resistance relative to the increase in the amount of resin contained per unit area of ​​the porous layer and the increase in the amount of insulation resistance relative to the increase in the amount of polyolefin contained per unit area of ​​the porous film is recorded. Patent document 4 also records that when the porous layer is formed as a functional layer, it can have a specific dynamic friction coefficient.

[0009] Prior art literature

[0010] Patent Literature

[0011] Patent Document 1: Korean Patent Publication No. 10-2016-0118979

[0012] Patent Document 2: International Publication No. 2020 / 175079

[0013] Patent Document 3: International Publication No. 2021 / 085144

[0014] Patent Document 4: International Publication No. 2016 / 031466 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] However, these previous separators have the following problems. For example, in Patent Document 1, due to the poor dispersibility of the adhesive polymer in the coating state, there are the following problems: a portion where the adhesive polymer aggregates is generated on the separator, and the adhesion to the electrode is uneven, which leads to a problem of reduced overall adhesion and a problem of deterioration of heat resistance (heat shrinkage resistance). In Patent Documents 2 and 3, the adhesion of the covering layer is insufficient, and there is still room for improvement in the suppression of powder loss in the manufacturing process and the adhesion to the electrode. It should be noted that even if the technology described in Patent Document 4 is related to the productivity of non-aqueous secondary batteries with electrodes, there is still room for improvement in the productivity of separators for non-aqueous secondary batteries.

[0017] Furthermore, along with the improvement of electrode materials, high-density assembly of multiple non-aqueous secondary batteries (single cells) (increasing the volume energy density of the assembly), etc., there is still a demand for improved output characteristics (rate characteristics) and / or cycle characteristics of batteries including separators.

[0018] In view of the above circumstances, an object of the present application is to provide a separator for an electrical storage device capable of achieving improved productivity, and an electrical storage device including the separator.

[0019] Solutions for solving problems

[0020] Examples of implementations of the present application are listed below. [1]

[0022] A separator for an electrical storage device, comprising a substrate and a covering layer, wherein the substrate is a polyolefin microporous membrane containing polyolefin as a main component, and the covering layer is arranged on at least one surface of the substrate.

[0023] The aforementioned covering layer comprises a granular polymer of an inorganic filler and a thermoplastic polymer,

[0024] The aforementioned particulate polymer includes particulate polymer protruding from the surface of the aforementioned inorganic filler portion,

[0025] The static friction coefficient of the coating layer is 0.40 or more and 0.60 or less. [2]

[0027] The electrical storage device separator according to Item 1, wherein a portion of the surface of the protruding particulate polymer is defective. [3]

[0029] The electrical storage device separator according to item 1 or 2, wherein the ratio of the area of ​​the particulate polymer falling-off portion to the total area of ​​the particulate polymer in surface observation of the covering layer is 10% or less. [4]

[0031] The electrical storage device separator according to any one of items 1 to 3, wherein the cover layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer.

[0032] When the thickness of the inorganic filler portion is L1 and the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler formed in the inclined shape is L2, the average value of the inclination rate L2 / L1 of the covering layer is not less than 1.2. [5]

[0034] The electrical storage device separator according to any one of items 1 to 4, wherein the cover layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer.

[0035] When the thickness of the aforementioned inorganic filler portion is set to L1, the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the aforementioned inorganic filler formed in the aforementioned inclined shape is set to L2, and the maximum distance from the boundary line between the substrate and the covering layer to the outline of the aforementioned protruding granular polymer is set to L3, the average value of the coverage rate of the aforementioned protruding granular polymer (L2-L1) / (L3-L1) is greater than 0.4. [6]

[0037] The electrical storage device separator according to any one of items 1 to 5, wherein 20% or more of the protruding particulate polymer is in contact with the surface of the substrate. [7]

[0039] The electrical storage device separator according to any one of items 1 to 6, wherein the cover layer has a 180° peel strength from the substrate of 200 gf / cm or more. [8]

[0041] The electrical storage device separator according to any one of items 1 to 7, wherein the area of ​​the Voronoi polygon obtained by performing Voronoi segmentation with the protruding particulate polymer as a generator in the surface observation of the covering layer (s i ) has a coefficient of variation (cv) of 0.10 or more and 0.60 or less. [9]

[0043] The electrical storage device separator according to any one of items 1 to 8, wherein the number of the protruding particulate polymers is 50% or more of the total number of the particulate polymers contained in the covering layer.

[10]

[0045] The electrical storage device separator according to any one of items 1 to 9, wherein the particle size distribution of the particulate polymer is 1.1 or less.

[11]

[0047] The electrical storage device separator according to any one of items 1 to 10, wherein the particulate polymer is a primary particle.

[12]

[0049] The electrical storage device separator according to Item 11, wherein the average particle diameter of the primary particles is 1 μm or more and 10 μm or less.

[13]

[0051] The electrical storage device separator according to any one of items 1 to 12, wherein the heat shrinkage ratio in TD at 130° C. for 1 hour is 5% or less.

[14]

[0053] The electrical storage device separator according to any one of items 1 to 13, wherein the heat shrinkage rate in TD at 150° C. for 1 hour is 5% or less.

[15]

[0055] The electrical storage device separator according to any one of items 1 to 14, wherein the amount of the particulate polymer is 1 part by mass or more and 50 parts by mass or less relative to 100 parts by mass of the inorganic filler contained in the covering layer.

[16]

[0057] The electrical storage device separator according to any one of items 1 to 15, wherein the protruding particulate polymer protrudes by 0.1 times or more the thickness of the inorganic filler portion.

[17]

[0059] The electrical storage device separator according to any one of items 1 to 16, wherein the protruding particulate polymer contains at least one selected from the group consisting of a copolymer containing a (meth)acrylic acid ester as a monomer, a styrene butadiene copolymer, and a copolymer containing a fluorine atom.

[18]

[0061] The electrical storage device separator according to any one of items 1 to 17, wherein the protruding particulate polymer contains a copolymer containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers.

[19]

[0063] The electrical storage device separator according to any one of Items 1 to 18, wherein the protruding particulate polymer contains a copolymer containing a polyfunctional (meth)acrylate as a monomer.

[20]

[0065] The electrical storage device separator according to any one of items 1 to 19, wherein a dichloromethane-soluble component in the electrical storage device separator is 0.05 mass % or more and 0.80 mass % or less based on the total mass of the electrical storage device separator. [twenty one]

[0067] The electrical storage device separator according to any one of items 1 to 20, wherein a total amount of metal cations contained in the covering layer is 0.1 ppm or more and 100 ppm or less based on the total mass of the covering layer. [twenty two]

[0069] An electric storage device comprising the electric storage device separator according to any one of items 1 to 21.

[0070] Effects of the Invention

[0071] According to the present application, it is possible to prevent the winding deviation of the separator for storage device, prevent the winding deviation of the separator for storage device and the electrode winding body, and / or improve the grip of the film and roll such as the separator for storage device in the manufacture of the separator for storage device or the storage device, and transport the film with low tension during separation, thereby reducing or eliminating the curling of the separator in the length direction (MD), thereby improving the productivity of the separator for storage device. BRIEF DESCRIPTION OF THE DRAWINGS

[0072] Figure 1 It is a schematic diagram of the surface of the cover layer in this embodiment.

[0073] Figure 2 for Figure 1 Schematic diagram of the AA section.

[0074] Figure 3 This is a schematic diagram showing an example of observing the surface of the cover layer in this embodiment.

[0075] Figure 4 For Figure 3 An example of the results of determination of protruding particulate polymer.

[0076] Figure 5 For Figure 4 An example of the result of Voronoi segmentation.

[0077] Figure 6 For Figure 5 An example of the result of extracting the Voronoi polygons corresponding to the closed area.

[0078] Figure 7This is an example of a method of setting 10 sections including 95 fields of view.

[0079] Figure 8 This is a schematic diagram for illustrating that a part of the surface of the particulate polymer protruding from the inorganic filler portion in the covering layer in the present embodiment is defective.

[0080] Fig. 9 A schematic diagram showing an inspection jig for evaluating step deviation and a winding body set therein. DETAILED DESCRIPTION

[0081] Hereinafter, an exemplary embodiment of the present application (hereinafter abbreviated as “the present embodiment”) will be described in detail, but the present application is not limited to the present embodiment.

[0082] In this specification, the longitudinal direction (MD) refers to the machine direction in which the microporous membrane is continuously formed, and the transverse direction (TD) refers to the direction crossing the MD of the microporous membrane at an angle of 90°.

[0083] In this specification, the upper limit and lower limit of each numerical range can be combined arbitrarily. In addition, a certain component contains a specific component as a main component, which means that the content of the specific component constitutes the most mass of the mass of the component. Unless otherwise specified, the physical properties or numerical values ​​recorded in this specification are measured or calculated by the method described in the embodiments. For greater clarity, the scale, shape and length of each part shown in the drawings are sometimes enlarged.

[0084] 《Separators for power storage equipment》

[0085] The electrical storage device separator of the present embodiment includes a substrate which is a polyolefin microporous membrane containing polyolefin as a main component and a covering layer disposed on at least one surface of the substrate. The covering layer includes an inorganic filler and a granular polymer of a thermoplastic polymer.

[0086] 〈Amount of granular polymer〉

[0087] The amount of the granular polymer is 1 mass part or more and 50 mass parts or less relative to 100 mass parts of the inorganic filler, preferably 3 mass parts or more and 50 mass parts or less, more preferably 5 mass parts or more and 20 mass parts or less, and further preferably 5 mass parts or more and 15 mass parts or less. By making the amount of the granular polymer 1 mass part or more and 50 mass parts or less, it is possible to maintain ion permeability and improve adhesion to the electrode. From the viewpoint of improving heat shrinkage resistance, it is preferably 10 mass parts or less.

[0088] 〈Protrusion amount of granular polymer〉

[0089] The particulate polymer may contain the particulate polymer in an amount not less than 0.1 times the thickness of the inorganic filler portion protruding from the cover layer.

[0090] In this specification, the "thickness of the inorganic filler portion" refers to the distance (L1) between the surface of the polyolefin microporous membrane and the outermost surface of the layer (layer formed by the inorganic filler) formed by the accumulation of inorganic fillers stacked thereon, and is measured based on the SEM image of the cross section of the covering layer. It should be noted that the "inorganic filler portion" refers to: when the diameter of each protruding granular polymer is set to D, the portion that does not contain granular polymers is 1.5D or more from the center of each protruding granular polymer in the horizontal direction (the surface direction of the covering layer). The measurement conditions are described in the first embodiment column.

[0091] By making the protrusion of the granular polymer more than 0.1 times the thickness of the inorganic filler part, the adhesion to the electrode can be improved. In addition, by making the protrusion of the granular polymer more than 0.1 times the thickness of the inorganic filler part, a gap is formed between the separator and the electrode. Utilizing this gap, the influence of expansion / contraction of the electrode with the charging and discharging of the storage device can be alleviated, the deformation of the winding body can be suppressed, and the cycle characteristics can be improved. From this viewpoint, the protrusion of the granular polymer is preferably more than 0.2 times and more than 0.3 times. From the viewpoint of suppressing the granular polymer from falling off the separator, the protrusion of the granular polymer is preferably less than 5 times, more preferably less than 4 times, less than 3 times, less than 2 times, less than 1 time, and less than 0.4 times.

[0092] In this specification, "protrusion" means: the granular polymer protrudes toward the surface side of the covering layer beyond the "thickness of the inorganic filler part". In the protruding part of the granular polymer (hereinafter referred to as the "protruding part"), a part of the protruding part can be covered with the inorganic filler. From the viewpoint of preventing the granular polymer from sliding off the covering layer and obtaining a higher adhesive force, it is preferred that a part of the periphery of the protruding part is covered with the inorganic filler. In addition, from the viewpoint of ensuring the contact area between the granular polymer and the electrode and obtaining a higher adhesive force, it is preferred that the central part of the protruding part is exposed on the surface of the covering layer.

[0093] In this specification, "a state in which the granular polymer protrudes 0.1 times or more of the thickness of the inorganic filler portion" means that, when the thickness of the inorganic filler portion measured from the SEM image of the cross section of the covering layer is L1 and the maximum distance from the boundary line between the substrate and the covering layer to the outline of the protruding granular polymer is L3, the average value of the ratio (L3-L1) / L1 is 0.1 or more. In this specification, "the maximum distance from the boundary line between the substrate and the covering layer to the outline of the protruding granular polymer" means the distance from the boundary line between the substrate and the covering layer to the farthest point in the outline of the protruding granular polymer.

[0094] In other words, in this specification, "a state in which the granular polymer protrudes from the covering layer by more than 0.1 times the thickness of the inorganic filler portion of the covering layer" means that the maximum distance (L3) from the boundary line between the substrate and the covering layer to the outline of the protruding granular polymer measured based on the SEM image of the cross-section of the covering layer is more than 1.1 times the thickness (L1) of the inorganic filler portion of the covering layer.

[0095] The number of protruding granular polymers is preferably 50% or more of the total number of granular polymers contained in the covering layer. Thus, the effect brought about by the protruding granular polymers can be appropriately obtained. The ratio of the number of protruding granular polymers to the total number of granular polymers contained in the covering layer (the number of protruding granular polymers / the total number of granular polymers) is also expressed as a protrusion ratio, which is positioned as one of the indicators of the protrusion degree of the granular polymer in the covering layer. The protrusion ratio is more preferably 60% or more, 70% or more, or 80% or more, and the theoretical upper limit is 100%.

[0096] <Inclined morphology of the covering layer, contact ratio between the granular polymer and the substrate, and 180° peel strength>

[0097] The electrical storage device separator of the present embodiment preferably has one or more of the following features (1) to (3).

[0098] (1) The covering layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer;

[0099] (2) more than 20% of the protruding particulate polymer contacts the surface of the substrate;

[0100] (3) The 180° peel strength of the cover layer from the substrate (hereinafter also referred to as “180° peel strength”) is 200 gf / cm or more;

[0101] Features(1):

[0102] The separator for the storage device preferably has a covering layer formed in an inclined shape in a manner that becomes thicker toward the protruding granular polymer. Thus, the granular polymer can be prevented from sliding off the covering layer, and the adhesion to the electrode is improved. In the present application specification, "inclined" means: when the thickness of the inorganic filler portion of the covering layer is set to L1, and the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler formed into the inclined covering layer is set to L2, the average value of the inclination rate L2 / L1 of the covering layer is 1.1 (e.g., 1.10) or more.

[0103] As an example of the relationship between L1 and L2, see Figure 2Schematic diagram of the invention. The inclination is preferably that the thickness of the covering layer changes continuously in a manner that the covering layer gradually thickens toward the protruding granular polymer, and preferably does not include discontinuous changes due to the lack of the covering layer. There is a tendency for the heat resistance and / or cycle characteristics to be improved due to the absence of the lack of the covering layer. The inclination may be more gentle the farther away from the protruding granular polymer, and more steep the protruding portion closer to the protruding granular polymer.

[0104] In addition, when the inorganic filler covers a part of the protrusion, the inclination on the protrusion can become gentle again toward the center of the protrusion. The average value of the inclination rate L2 / L1 of the covering layer is preferably 1.2 (e.g., 1.20) or more, 1.3 (e.g., 1.30) or more, 1.4 (e.g., 1.40) or more, 1.5 (e.g., 1.50) or more, or 1.7 (e.g., 1.70) or more.

[0105] By forming the covering layer in an inclined shape so as to become thicker toward the protruding particulate polymer, the inorganic filler can exist along the contour of the particulate polymer and cover a part of the protruding portion. The inorganic filler preferably exists along the contour of the particulate polymer and covers a part of the periphery of the protruding portion.

[0106] In addition, it is preferred that the center of the protruding portion is exposed on the surface of the covering layer. When the maximum distance from the boundary line of the substrate-covering layer to the outline of the protruding granular polymer (the distance from the boundary line of the substrate-covering layer to the farthest point in the outline of the protruding granular polymer) is set to L3, the average value of the coverage of the protruding portion (L2-L1) / (L3-L1) is preferably 0.4 (e.g., 0.40) or more.

[0107] As an example, the relationship between L1, L2 and L3 can be seen in Figure 2 Schematic diagram of. By making the average value of the inclination rate L2 / L1 greater than 1.1 or the average value of the coverage rate (L2-L1) / (L3-L1) greater than 0.4, the particulate polymer is prevented from sliding off the covering layer, and the adhesion to the electrode is improved. From the viewpoint of ensuring the bonding area between the particulate polymer and the electrode and improving the adhesion to the electrode, the upper limit of the average value of the inclination rate L2 / L1 can be 5.0 or less, 4.0 or less, 3.0 or less, 2.8 or less, 2.5 or less, 2.3 or less, 2.0 or less, or 1.8 or less.

[0108] In addition, the upper limit of the coverage (L2-L1) / (L3-L1) is preferably less than 1.0 (e.g., 1.00), less than 0.9 (e.g., 0.90), less than 0.8 (e.g., 0.80), or less than 0.7 (e.g., 0.70). A coverage of 1.0 or more means that the inorganic filler present in the protruding portion of the granular polymer reaches the uppermost portion of the contour of the protruding granular polymer (the point farthest from the boundary line between the substrate and the covering layer). By making the coverage lower than 1.0, the contact area between the granular polymer and the electrode is ensured, and the adhesion to the electrode is improved. By making the coverage less than 0.8, the contact area between the granular polymer and the electrode becomes larger, and the adhesion to the electrode is further improved.

[0109] Features (2):

[0110] In the separator for storage device, the contact rate between the protruding granular polymer and the surface of the substrate is preferably 20% or more, more preferably 50% or more, and further preferably 70% or more. The "contact rate" is calculated based on the image of the cross section of the covering layer of the separator for storage device observed by SEM. By increasing the granular polymer protruding and in contact with the substrate, the bonding force between the substrate and the granular polymer is further improved, the 180° peel strength is improved, and the bonding force with the electrode is improved. The upper limit of the contact rate between the protruding granular polymer and the surface of the substrate can be less than 100% or 100%.

[0111] Features (3):

[0112] The 180° peel strength of the separator for storage device is preferably 200 gf / cm or more, more preferably 230 gf / cm or more, and further preferably 250 gf / cm or more. "180° peel strength" refers to the strength when the covering layer is peeled off in a manner that the surface of the covering layer facing the substrate is 180° relative to the substrate. By making the 180° peel strength 200 gf / cm or more, the adhesion to the electrode is improved and thermal shrinkage is suppressed. The upper limit of the 180° peel strength can be 500 gf / cm or less.

[0113] The separator for storage device of this embodiment may have any combination of the above-mentioned features (1) to (3), that is, it may have: (1) and (2); (1) and (3); (2) and (3); a combination of (1), (2) and (3). Among these, from the viewpoint of higher adhesion and smaller thermal shrinkage, the combination of (1), (2) and (3) is preferred, that is, the covering layer is formed in an inclined shape so as to become thicker toward the protruding granular polymer, the contact rate between the protruding granular polymer and the substrate surface is 20% or more, and the 180° peel strength is 200 gf / cm or more.

[0114] Here, the electrical storage device separator of the present embodiment has the following features (4) and / or (5) in addition to the above features (1) to (3) or in combination with any of the above features (1) to (3).

[0115] Features (4):

[0116] In the separator for a storage device, in the surface observation of the cover layer, the area of ​​the Voronoi polygon obtained by performing Voronoi segmentation with the protruding particulate polymer as the generator point (s i ) is 0.10 or more and 0.60 or less. In the covering layer where the coefficient of variation (cv) is within this range, the uniformity of the distribution of the protruding particulate polymer is high. The coefficient of variation (cv) is preferably 0.20 or more, 0.25 or more, and 0.30 or more, and preferably 0.55 or less, 0.50 or less, and 0.45 or less.

[0117] In the separator having the above-mentioned feature (4), the uniformity of distribution of the protruding granular polymer is high, and accordingly, the uniformity of distribution of the region between the protruding granular polymer is also high. Therefore, if a separator having the above-mentioned feature (4) is used, the uniformity of in-plane distribution of lithium ions moving through the region between the electrodes can be improved, thereby achieving improvement in rate characteristics and / or cycle characteristics.

[0118] In addition, in the separator having the above-mentioned feature (4), corresponding to the high uniformity of the distribution of the protruding granular polymer, the uniformity of the distribution is also high in the contact area between the protruding granular polymer and the electrode before or after the heat pressing process. Therefore, if the separator having the above-mentioned feature (4) is used, the uniformity of the in-plane distribution of the stress of the protruding granular polymer applied to the electrode can be improved, and the adhesion to the electrode can be improved.

[0119] In addition, in the separator having the above-mentioned feature (4), the uniformity of distribution of the protruding granular polymer is high, and the uniformity of distribution of the inorganic filler having a heat-resistant function is also high. Therefore, if the separator having the above-mentioned feature (4) is used, the uniformity of in-plane distribution based on the heat-resistant performance of the inorganic filler can be improved, and the heat shrinkage resistance can be improved.

[0120] Here, in the past, it was believed that "adhesion to the electrode" and "resistance to heat shrinkage" are sometimes in a trade-off relationship, and in addition, it was believed that "adhesion to the electrode" and "rate characteristics" and / or "cycle characteristics" are sometimes in a trade-off relationship. Specifically, it is believed that since the granular polymer does not have sufficient heat resistance, if the content of the granular polymer is increased in order to improve the "adhesion to the electrode", it is difficult to achieve an improvement in the "resistance to heat shrinkage". In addition, it is believed that the presence of the granular polymer forms an impedance for ions, so if the content of the granular polymer is increased, it is difficult to achieve an improvement in the "rate characteristics" and / or "cycle characteristics". With regard to these aspects, according to the present embodiment, by adjusting the above-mentioned coefficient of variation (cv) to a specified range, it is possible to take into account the improvement of the adhesion to the electrode, the improvement of the resistance to heat shrinkage, and the improvement of the rate characteristics and / or cycle characteristics of the storage device as described above.

[0121] As a means of adjusting the above-mentioned coefficient of variation (cv) to the above-mentioned range, for example, the particle size and content of the thermoplastic polymer in the coating liquid applied to the substrate, the viscosity and coating amount of the coating liquid, and the coating method and coating conditions can be changed. For example, the following methods can be cited: adjusting the viscosity of the coating liquid applied to the substrate to a specified range; reducing the particle size of the thermoplastic polymer in the coating liquid; stirring based on turbulence when supplying the coating liquid to the substrate in the coating process; subjecting the coating liquid applied to the substrate to ultrasonic treatment; etc.

[0122] "Voronoi segmentation" means dividing regions according to which mother point other points in the same space are close to, relative to a plurality of points (mother points) arranged at arbitrary positions in a certain distance space. A graph containing the regions thus obtained is called a Voronoi diagram. In a Voronoi diagram, the boundary lines of a plurality of regions become part of the bisectors of each mother point, and each region forms a polygon (Voronoi polygon). Here, in this specification, the mother point is a "protruding granular polymer", and further, it is the center point of the protruding portion of the protruding granular polymer in surface observation.

[0123] In the observation field of the covering layer, one protruding granular polymer is regarded as one circle with an average diameter (l). In addition, perpendicular bisectors are drawn between adjacent multiple protruding granular polymers, and for each polymer, the polygon surrounded by the above-mentioned perpendicular bisectors is called a "Voronoi polygon". When Voronoi segmentation is performed in the observation field, the unenclosed area is not treated as a processing object. As an unenclosed area, for example, there can be listed: when a polymer exists at the boundary of the observation field and the entire protruding part of the polymer is not observed, the area obtained by Voronoi segmentation of the polymer.

[0124] The area of ​​the Voronoi polygon (s i) can be actually measured by image analysis as needed, and the area of ​​the Voronoi polygon (s i ) divided by the total number of the Voronoi polygons to be processed (n), the area (s i ) is the average value (m). Next, according to the area of ​​the Voronoi polygon (s i ), the total number (n) and average value (m) of the Voronoi polygons of the processed object, and the area (s) of the Voronoi polygons obtained by conventional methods i ) standard deviation (sd). The area of ​​the Voronoi polygon (s i The coefficient of variation (cv) of ) is calculated by the following formula:

[0125] Coefficient of variation (cv) = standard deviation (sd) / mean (m)

[0126] The above-mentioned coefficient of variation (cv) is considered to represent the in-plane distribution or aggregation state of the protruding granular polymer. When the above-mentioned coefficient of variation (cv) is 0.10 or more, it can be evaluated that the protruding granular polymer is randomly dispersed and arranged on the surface of the covering layer. When the above-mentioned coefficient of variation (cv) is 0.60 or less, it can be evaluated that the protruding granular polymer is not excessively aggregated.

[0127] The means for observing the covering layer is preferably appropriately selected according to the size or distribution state of the thermoplastic polymer. In addition, as for the microscope, an electron microscope, an atomic force microscope, an optical microscope, a differential interference microscope, etc. can be used. Among these, when dealing with the distribution state of dispersed particles such as the present embodiment, an electron microscope or an atomic force microscope is preferably used. The means for observing the covering layer particularly adopts the technique shown in the first embodiment.

[0128] The average observation field of the covering layer should be ensured within the observation field. In addition, the projection area in the observation field should be appropriately adjusted to grasp the average distribution state of the protruding granular polymer. For example, the protruding granular polymer used as the treatment object is preferably about 80 to 200 per field of view. The observation field can be obtained by observing the covering layer using a pre-set observation method and magnification. For example, Figure 3 This is a schematic diagram of an example of observing the surface of the coating layer using a scanning electron microscope at a magnification of 1000. The dispersion state of the thermoplastic polymer particles can be analyzed by Voronoi segmentation.

[0129] In the observation using a scanning electron microscope, an appropriate magnification is set in the analysis based on Voronoi segmentation according to the particle size of the thermoplastic polymer particles. Specifically, the magnification is set as follows: the number of thermoplastic polymer particles observed in one field of view is preferably 40 or more and 300 or less, more preferably 60 or more and 240 or less, and further preferably 80 or more and 200 or less. Thus, the analysis based on Voronoi segmentation can be appropriately performed. For example, if the content of thermoplastic polymer particles with a particle size of about 2.0 μm is about 10 parts by mass relative to 100 parts by mass of the inorganic filler of the covering layer, it is appropriate to set the magnification to 5000 times, and if the content of thermoplastic polymer particles with a particle size of about 3.5 μm is about 10 parts by mass relative to 100 parts by mass of the inorganic filler of the covering layer, then the magnification setting of about 1000 times is appropriate for the analysis based on Voronoi segmentation.

[0130] The protruding particulate polymer contained in the observation field obtained by the above observation method is identified. For example, the protruding particulate polymer is identified from the observation field by naked eyes or by using image processing software. Figure 4 To illustrate the use of image processing software to determine Figure 3 An example of the results of protruding granular polymers contained in the observation field.

[0131] For the protruding granular polymer determined by surface observation of the covering layer, Voronoi segmentation can be performed as defined above. Specifically, the surface of the coating film after the substrate is coated with a coating liquid containing a thermoplastic polymer is photographed to obtain an image. The protruding portion of the protruding granular polymer determined in the obtained image is regarded as a circle with an average diameter (l(L)), and Voronoi segmentation is performed, thereby making it possible to draw a Voronoi polygon. For example, the Voronoi polygon can be drawn manually or using image processing software. Then, the area (si) of the drawn Voronoi polygon is calculated.

[0132] For example, Figure 5 For Figure 4 An example of the Voronoi polygons obtained by performing Voronoi segmentation on the protruding granular polymer identified in the figure. Figure 5 The results of the Voronoi polygons corresponding to the enclosed areas in the Voronoi polygons shown are shown in Figure 6 .

[0133] Using the above observation method and image processing method, the total number of protruding granular polymers in the observation field and the area of ​​the Voronoi polygon (s i). Then, the above-mentioned coefficient of variation (cv) can be calculated as described above. The distribution of the protruding granular polymer sometimes changes depending on the observation field of view. Therefore, the above-mentioned coefficient of variation (cv) is preferably an average value of the values ​​calculated for a plurality of observation fields of view. As the number of fields of view, it is preferably set to 3 or more.

[0134] It is particularly preferable to use the average value of the values ​​calculated for 10 viewing fields determined as described below.

[0135] i) Each measurement field: Image taken with a scanning electron microscope

[0136] ii) How to set the field of view:

[0137] a) Set the starting point horizon,

[0138] b) A total of 10 fields of view including 9 fields of view consisting of areas sequentially adjacent to the field of view of the starting point at intervals of 5 mm in a single axis direction and the field of view of the starting point are set as the fields of view for measurement.

[0139] Each of the measurement fields is preferably a photographed image that is set and photographed at a magnification such that the number of protruding particulate polymers observed in one field is 80 or more and 200 or less.

[0140] Below, refer to Figure 7 A preferred method for setting the ten viewing fields in this embodiment will be described.

[0141] i) As the captured image, as described above, an image captured by a scanning electron microscope at a magnification of 1000 times can be used. Figure 7 In the image, first, set the field of view (I) of the starting point. One field of view is composed of an image taken by a scanning electron microscope with a magnification of 1000 times, so the scale of this one field of view is about 100μm×100μm, which constitutes a field of view suitable for Voronoi segmentation evaluation based on protruding granular polymers. Next, set 9 fields of view (II~X) adjacent to each other in a single axis at intervals of 5mm relative to the field of view (I) of the aforementioned starting point. These fields of view (II~X) are respectively composed of images taken with the same magnification as the field of view (I) of the starting point.

[0142] The surface observation of the above-mentioned covering layer is preferably carried out on the area that does not participate in ion conduction. For example, the covering layer in the separator in the state just after manufacture and not yet assembled into the storage element can be observed. During or after the use of the storage element, it is also a preferred method in this embodiment to observe the so-called "ear" part of the separator (the area near the outer edge of the separator and not participating in ion conduction). As understood from the above-mentioned evaluation method, when 10 fields of view are used as the observation object, a separator piece with a length of about 45 mm is used as the measurement object, so that the dispersion state of the thermoplastic polymer on its surface can be accurately evaluated.

[0143] It is speculated that the ability to perform Voronoi segmentation as described above means that the granular polymer does not substantially overlap in the covering layer, but exists in the form of a single layer of particles. For example, in the case where the granular polymer overlaps with each other in several layers in the covering layer, the concept of the area occupied by a single particle does not hold true, and thus Voronoi segmentation cannot be performed.

[0144] In the separator of the present embodiment, it is preferred that the above-mentioned requirements are adjusted to the above-mentioned ranges, respectively, while the particulate polymers in the covering layer are arranged so as not to substantially overlap.

[0145] The presence form (pattern) of the covering layer on the substrate is preferably that the granular polymer is mutually dispersed over the entire surface of the substrate. The granular polymer may also form a cluster in a part of the region, but it is preferred that the granular polymer is appropriately dispersed to the extent that the above-mentioned coefficient of variation (cv) is satisfied as a whole. It is preferred that the granular polymer is appropriately dispersed to the extent that the above-mentioned coefficient of variation (cv) is satisfied as a whole.

[0146] Features (5):

[0147] In the separator for an electrical storage device, the static friction coefficient of the covering layer is 0.40 or more and 0.60 or less. When the static friction coefficient of the covering layer is within this range, the winding deviation of the separator for an electrical storage device can be prevented, and / or the winding deviation of the separator for an electrical storage device and the winding body of the electrode can be prevented, thereby improving the productivity of the separator for an electrical storage device.

[0148] In addition, when the static friction coefficient of the covering layer of the separator for storage device with feature (5) is within the range of greater than 0.40 and less than 0.60, for example, the grip of the film and roll of the separator for storage device or the storage device can be improved in the manufacture of the separator for storage device or the storage device, and the film can be transported with low tension during cutting, which can reduce or eliminate the MD curl of the separator, thereby improving productivity.

[0149] From the viewpoint of further improving the productivity of the electrical storage device separator, the static friction coefficient of the covering layer is preferably 0.41 to 0.59, more preferably 0.41 to 0.57, and even more preferably 0.41 to 0.55.

[0150] In the separator for a storage device having the feature (5), the granular polymer protruding from the surface of the inorganic filler portion contained in the covering layer is composed of a thermoplastic polymer, and the protruding granular polymer preferably has a defect in a portion of its surface. If a portion of the surface of the protruding granular polymer has a defect, an exposed area of ​​the thermoplastic polymer sufficient to prevent winding deviation and improve gripping of the roll and gripping of the electrode can be ensured when the separator is wound or when the storage device is manufactured.

[0151] In this specification, the particulate polymer protruding from the surface has a defect, which means that the exposed surface of at least one of the protruding polymer particles does not form a spherical surface, or a part of the exposed surface has a discontinuous surface. When the separator for the storage device is wound to form a wound body, the partial defect of the surface of the particulate polymer protruding from the surface of the inorganic filler part contained in the covering layer can increase the contact area between the wound body and the protruding particulate polymer, and further can prevent the winding deviation of the separator and improve productivity. Figure 8 Schematic diagram for illustrating that a part of the surface of the granular polymer protruding from the inorganic filler portion in the covering layer of the separator for storage device having feature (5) is defective. For example, when the cross-sectional observation of the protruding granular polymer can be observed in the form of a trapezoid, parallelogram or polygon, a part of the surface of the protruding granular polymer may be defective. Among them, from the viewpoint of further improving the productivity of the separator for storage device, it is more preferable as follows Figure 8 (a) of the sphere composed of granular polymers, a portion of the surface of which is cut off on a plane, such as Figure 8 A shape in which a part of the spherical surface has a planar region as in (b), or a shape in which a part of the spherical surface composed of a particulate polymer is defective.

[0152] From the same viewpoint as above, the defect rate of the spherical surface of the protruding particulate polymer is preferably in the range of 0.74 to 0.93. In addition, in the surface observation of the covering layer, the ratio of the area of ​​the particulate polymer falling-off portion to the total area of ​​the particulate polymer is preferably 10% or less, more preferably less than 0.1%, for example, 0%. The method for calculating the defect rate, the method for surface observation of the covering layer, and the method for calculating the ratio of the area of ​​the particulate polymer falling-off portion to the total area of ​​the particulate polymer are described in detail in the Examples.

[0153] As means for adjusting the static friction coefficient of the covering layer to within the above range and / or making a part of the surface of the protruding granular polymer lacking, for example, the following can be listed: controlling the conditions of the coating / drying process of coating the substrate with the coating liquid in the manufacturing process of the separator for the storage battery device, such as the particle size and content of the thermoplastic polymer in the coating liquid coated on the substrate, the viscosity and coating amount of the coating liquid, and the coating method and coating conditions; or controlling the conditions after the coating / drying process, such as the pressure applied to the coating surface, the speed of the conveying roller with which the coating surface contacts, the shape of the inorganic filler in the covering layer, and the peel strength of the covering layer.

[0154] In more detail, means for controlling the conditions of the coating / drying process include, for example: adjusting the viscosity of the coating liquid applied to the substrate to a specified range; reducing the particle size of the thermoplastic polymer in the coating liquid; performing turbulent-based stirring when supplying the coating liquid to the substrate during the coating process; subjecting the coating liquid applied to the substrate to ultrasonic treatment; etc.

[0155] In more detail, the control means of the conditions after the coating / drying process include, for example: controlling the tension applied in the direction perpendicular to the surface of the conveying roller in contact with the coating surface to be above a specified value; making the conveying roller speed in contact with the coating surface lower than the conveying speed of the separator; forming the inorganic filler into an inclined shape in such a way that the protruding granular polymer does not slide off the surrounding inorganic filler part; increasing the peel strength of the covering layer; etc.

[0156] 〈Dichloromethane soluble components〉

[0157] In the separator for storage device of the present embodiment, the dichloromethane soluble component is based on the total mass of the separator for storage device, preferably 0.05 mass % or more and 0.80 mass % or less, more preferably 0.10 mass % or more and 0.60 mass % or less, and further preferably 0.15 mass % or more and 0.50 mass % or less. The "soluble component" of dichloromethane refers to: the component extracted into dichloromethane when the separator is immersed in dichloromethane. The plasticizer mixed in the manufacture of the substrate is mainly extracted as a dichloromethane soluble component. By containing more than 0.10 mass % of dichloromethane soluble components, the bonding force between the substrate and the covering layer is further improved, and it is easier to adjust the 180° peel strength to more than 200gf / cm. By making the dichloromethane soluble component less than 0.60 mass %, the internal resistance of the battery can be reduced. As a method for adjusting the dichloromethane soluble component to 0.05 mass % or more and 0.80 mass % or less, in the plasticizer extraction step when manufacturing the substrate, if it is an intermittent method, the adjustment of the extraction time, the type of extraction solvent, the temperature of the extraction solvent, the number of extractions, etc. can be listed; if it is a continuous method, the adjustment of the extraction time, the type of extraction solvent, the temperature of the extraction solvent, the supply amount of the extraction solvent, etc. can be listed.

[0158] 〈Metal cations〉

[0159] In the separator for storage device of the present embodiment, the total amount of metal cations contained in the covering layer is preferably 0.1 ppm or more and 100 ppm or less, more preferably 0.1 ppm or more and 70 ppm or less, and further preferably 0.1 ppm or more and 50 ppm or less, based on the total mass of the covering layer. If the total amount of metal cations is adjusted to be less, the inorganic filler and the granular polymer will be evenly dispersed and easily coated in the formation of the covering layer. As metal cations, sodium ions (Na + ), calcium ions (Ca 2+ ) and magnesium ions (Mg 2+ ) etc. As a method for adjusting the total amount of metal cations to 0.1 ppm or more and 100 ppm or less, a method of washing the filler to be the raw material of the covering layer with water before use can be cited. The washing frequency may be once or twice or more, and the more the washing frequency increases, the less the total amount of metal cations contained in the filler.

[0160] 〈Heat shrinkage ratio〉

[0161] The heat shrinkage rate of the electrical storage device separator of the present embodiment in TD at 130° C. for 1 hour is preferably 5% or less, more preferably 0% or more and 3% or less, and still more preferably 0% or more and 1% or less.

[0162] The heat shrinkage of the TD of the separator for storage devices of this embodiment at 150°C for 1 hour is preferably 5% or less, more preferably 0% or more and 3% or less, and further preferably 0% or more and 1% or less. Here, if the heat shrinkage of the TD is 5% or less, it is possible to more effectively suppress the occurrence of short circuits in parts other than the parts to which external force is applied when heat is generated due to short circuits during impact tests. As a result, it is possible to more reliably prevent the temperature rise of the entire battery and the smoke and fire that may occur as a result.

[0163] The heat shrinkage of the separator for storage device of the present embodiment can be adjusted by appropriately combining the stretching operation of the substrate and the heat treatment. In addition, while suppressing the heat shrinkage of TD, the heat shrinkage of MD is preferably 5% or less, more preferably 0% or more and 3% or less, and further preferably 0% or more and 1% or less.

[0164] <Air permeability of separator>

[0165] The air permeability of the electric storage device separator is preferably 10 seconds / 100 cm 3 Above and 10000 sec / 100cm 3 Less than 40 seconds / 100 cm3 Above and 500 seconds / 100cm 3 Below, more preferably 50 seconds / 100cm 3 Above and 250 seconds / 100cm 3 Below, particularly preferably 60 seconds / 100 cm 3 More than 200 seconds / 100cm 3 Below. Thus, high ion permeability can be obtained. Air permeability is the air permeability resistance measured according to JIS P-8117.

[0166] 〈Base Material〉

[0167] The substrate is a polyolefin microporous membrane containing polyolefin as a main component, and preferably has the following aspects (1), (2), or a combination thereof: (1) The membrane thickness is 1 μm to 30 μm, and the air permeability is 500 sec / 100 cm 3 The porosity after compression measured in a compression test under the conditions of temperature 70°C, pressure 8 MPa and compression time 3 minutes is 30% or more. (2) The long crystal period of the polyolefin microporous membrane measured by small angle X-ray scattering (SAXS) is 37.0 nm or more.

[0168] Method (1):

[0169] Without being bound by theory, it is believed that the polyolefin microporous membrane has a film thickness of 1 μm to 30 μm and has a speed of 500 sec / 100 cm 3 The following air permeability and 30% or more post-compression porosity can be achieved in the production of non-aqueous secondary batteries using polyolefin microporous membranes as separators, so that the resistance of the polyolefin microporous membrane can be reduced or the resistance increase can be suppressed after the pressurization process, thereby achieving high output and high cycle characteristics of the non-aqueous secondary battery. The use of polyolefin microporous membranes to suppress the increase in resistance is significant when electrodes that are easy to expand and contract are used in the cells of non-aqueous secondary batteries, and is more significant when high-capacity electrodes used in automotive batteries, etc., or negative electrodes containing silicon (Si) are used.

[0170] It is believed that the porosity after compression is related to the structure of the main component of the polyolefin microporous membrane that is responsible for reducing resistance and / or suppressing resistance increase in the non-aqueous secondary battery. From the viewpoint of the above description, the porosity of the polyolefin microporous membrane after compression is preferably 31% or more, more preferably 32% or more, and further preferably 33% or more. The upper limit of the porosity of the polyolefin microporous membrane after compression can be determined based on the porosity before compression, for example, it can be preferably 60% or less, and further preferably 50% or less.

[0171] The porosity after compression of the polyolefin microporous membrane can be adjusted to the numerical range described above by, for example, controlling the molecular weight of the polyolefin raw material, the molecular weight and content of the polyethylene raw material, the stretch ratio during the biaxial stretching process, the preheating coefficient during the biaxial stretching process, the stretching coefficient during the biaxial stretching process, the MD / TD stretching temperature during the biaxial stretching process, the heat setting temperature, etc. in the manufacturing process of the polyolefin microporous membrane. Alternatively, the porosity after compression of the polyolefin microporous membrane can be adjusted to the numerical range described above by controlling the molecular weight of the polyolefin raw material, the molecular weight and content of the polyethylene raw material, the stretch ratio during the biaxial stretching process, the preheating coefficient during the biaxial stretching process, the stretching coefficient during the biaxial stretching process, the ratio of the preheating coefficient to the stretching coefficient, etc.

[0172] From the perspective of determining the structure of the main component of the membrane that can reduce resistance and / or suppress resistance increase in a non-aqueous secondary battery and achieve high output and high cycle characteristics, it is preferred to compare the porosity of the polyolefin microporous membrane before and after the compression test. The preferred numerical range of the porosity of the polyolefin microporous membrane before the compression test or before the compression test (hereinafter referred to as "porosity") is as described below.

[0173] Method (2):

[0174] Without being bound by theory, by making the polyolefin microporous membrane have a crystal long period of more than 37.0nm, surprisingly, the structural uniformity and compression resistance of the polyolefin microporous membrane are improved, and the reaction uniformity in the non-aqueous secondary battery is also improved. Thus, it is believed that even after the pressurization process in the production of a non-aqueous secondary battery using a polyolefin microporous membrane as a separator, the high output and high cycle characteristics of the non-aqueous secondary battery can be achieved. The improvement of the structural uniformity and compression resistance of the polyolefin microporous membrane is significant for the use of electrodes that are easy to expand and shrink in the unit of the non-aqueous secondary battery, and is more significant in the case of a high-capacity electrode or a negative electrode containing silicon (Si) used in a vehicle-mounted battery, etc.

[0175] Without being bound by theory, it is believed that the long crystal period obtained by SAXS measurement is associated with the structure of polyethylene that improves the structural uniformity and compression resistance of the membrane and the reaction uniformity in the non-aqueous secondary battery. In addition, it is believed that the long crystal period of the polyolefin microporous membrane is associated with the porosity of the membrane after compression. From the viewpoint of the above description, the long crystal period of the polyolefin microporous membrane is preferably 37.0nm to 60.0nm, 38.0nm to 55.0nm, 40.0nm to 50.0nm, or 42.0nm to 50.0nm.

[0176] The crystal long period of the polyolefin microporous membrane can be adjusted within the numerical range described above by, for example, controlling the molecular weight of the polyolefin raw material, the molecular weight and content of the polyethylene raw material, the stretching ratio during the biaxial stretching process, the preheating coefficient during the biaxial stretching process, the stretching coefficient during the biaxial stretching process, the MD / TD stretching temperature during the biaxial stretching process, the heat setting temperature, etc. in the manufacturing process of the polyolefin microporous membrane.

[0177] The separator for storage device of the present embodiment has a substrate, and the substrate is a polyolefin microporous membrane containing polyolefin as a main component. "Containing ... as a main component" means that the mass of the object component (polyolefin) constitutes the largest mass of the entire substrate. Based on the total mass of the substrate, the content of polyolefin in the polyolefin microporous membrane is, for example, more than 50 parts by mass, preferably more than 75 parts by mass, more preferably more than 85 parts by mass, further preferably more than 90 parts by mass, further preferably more than 95 parts by mass, particularly preferably more than 98 parts by mass, and can also be 100 parts by mass.

[0178] Since polyolefin has excellent coating properties when the coating liquid is coated on the film, it is advantageous for further reducing the thickness of the separator, and can increase the active material ratio in the power storage device and increase the capacity per unit volume. The polyolefin microporous membrane can use a membrane that has been used as a separator substrate in the past, preferably a microporous membrane with fine pores that has no electronic conductivity but has ion conductivity and high organic solvent resistance.

[0179] The polyolefin may be a polyolefin that can be used in conventional extrusion, injection, inflation, and blow molding. Examples of the polyolefin include homopolymers using ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene as monomers, and copolymers and multi-stage polymers of two or more of these monomers. These homopolymers, copolymers, and multi-stage polymers may be used alone or in combination of two or more.

[0180] As polyolefins, from the viewpoint of reducing or suppressing an increase in the electrical resistance of the film, the compression resistance of the film and the structural uniformity, for example, polyethylene, polypropylene and polybutene can be listed, and more specifically, low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, ultra-high molecular weight polyethylene, isotactic polypropylene, atactic polypropylene, ethylene-propylene random copolymer, polybutene and ethylene-propylene rubber can be listed.

[0181] These can be used alone or in combination of two or more. Among these, as polyolefin, from the viewpoint of the closing property of the pores blocked by heat melting, at least one selected from the group consisting of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene and ultra-high molecular weight polyethylene is preferred. In particular, from the viewpoint of low melting point and high strength, high-density polyethylene is preferred, and more preferably a density of 0.93 g / cm3 measured according to JIS K 7112 is preferred. 3 Polyethylenes of the above. Examples of polymerization catalysts used to produce these polyethylenes include Ziegler-Natta catalysts, Phillips catalysts, and metallocene catalysts. The main component of the polyolefin is preferably polyethylene, and the content of polyethylene in the substrate relative to the total mass of the polyolefin is preferably 50 parts by mass or more.

[0182] In order to improve the heat resistance of the substrate, the polyolefin microporous membrane preferably contains polypropylene and polyolefins other than polypropylene. Examples of polyolefin resins other than polypropylene include homopolymers of ethylene, 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene, and copolymers and multi-stage polymers of two or more of these monomers.

[0183] The amount of polypropylene in the substrate can be 0% relative to the total mass of polyolefin (polypropylene / polyolefin), and is not particularly limited, but from the viewpoint of taking both heat resistance and good shutdown function into consideration, it is preferably 1 mass part or more and 35 mass parts or less, more preferably 3 mass parts or more and 20 mass parts or less, and further preferably 4 mass parts or more and 10 mass parts or less. From the same viewpoint, the content ratio of olefin resin other than polypropylene, such as polyethylene, relative to the total mass of polyolefin in the polyolefin microporous membrane (olefin resin other than polypropylene / polyolefin) is preferably 65 mass parts or more and 99 mass parts or less, more preferably 80 mass parts or more and 97 mass parts or less, and further preferably 90 mass parts or more and 96 mass parts or less.

[0184] From the viewpoints of crystallinity, high strength, compression resistance, etc. when forming a polyolefin microporous membrane for a non-aqueous secondary battery, the polyolefin microporous membrane is preferably a porous membrane formed by a polyethylene composition in which polyethylene accounts for more than 50% by mass and less than 100% by mass of the resin component constituting the microporous membrane. The proportion of polyethylene in the resin component constituting the porous membrane is more preferably more than 60% by mass and less than 100% by mass, further preferably more than 70% by mass and less than 100% by mass, and further preferably more than 90% by mass and less than 100% by mass.

[0185] The viscosity average molecular weight of the polyolefin is preferably 30,000 to 6,000,000, more preferably 80,000 to 3,000,000, and further preferably 150,000 to 2,000,000. When the viscosity average molecular weight is 30,000 or more, there is a tendency to further increase the strength by entanglement of the polymers, so it is preferred. On the other hand, when the viscosity average molecular weight is 6,000,000 or less, it is preferred from the viewpoint of easy uniform melt kneading and improved formability in the extrusion and stretching process. Furthermore, if the viscosity average molecular weight is less than 1,000,000, there is a tendency to easily block the holes when the temperature rises and to obtain a better closing function, so it is preferred.

[0186] When the polyolefin microporous film includes polyethylene as the main component, from the viewpoint of the orientation and rigidity of the film, the lower limit of the viscosity average molecular weight (Mv) of at least one polyethylene is preferably 600,000 or more, more preferably 700,000 or more, and the upper limit of the Mv of polyethylene can be, for example, 2 million or less. From the same viewpoint, the proportion of polyethylene with Mv700,000 or more in the polyolefin resin constituting the polyolefin microporous film is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, or 100% by mass. From the viewpoint of the reduced fluidity during the melting of the film and the short-circuit resistance during the nail penetration test, the proportion of polyethylene with Mv600,000 or more in the polyolefin resin constituting the polyolefin microporous film is preferably 30% by mass or more, more preferably 50% by mass or more, further preferably 60% by mass or more, further preferably 70% by mass or more, or 100% by mass.

[0187] The viscosity average molecular weight (Mv) was calculated from the intrinsic viscosity [η] measured at a measurement temperature of 135° C. using decalin as a solvent according to ASTM-D4020 using the following formula.

[0188] Polyethylene: [η] = 6.77 × 10 -4 Mv 0.67 (Chiang formula)

[0189] Polypropylene: [η] = 1.10 × 10 -4 Mv 0.80

[0190] For example, instead of using a polyolefin having a viscosity average molecular weight of less than 1 million alone, a mixture of a polyolefin having a viscosity average molecular weight of 2 million and a polyolefin having a viscosity average molecular weight of 270,000 may be used, and the viscosity average molecular weight of the mixture may be less than 1 million.

[0191] The substrate may contain other resins besides polyolefin, for example, polyethylene terephthalate, polycycloolefin, polyethersulfone, polyamide, polyimide, polyimideamide, polyaramid, polycycloolefin, nylon, polytetrafluoroethylene and the like.

[0192] The substrate may contain optional additives. Such additives are not particularly limited, and examples thereof include: plasticizers, polymers other than polyolefins; inorganic particles; antioxidants such as phenolic, phosphorus, and sulfur; metal soaps such as calcium stearate and zinc stearate; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; and coloring pigments. The total content of these additives is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, and further preferably 5 parts by mass or less relative to 100 parts by mass of the polyolefin resin in the polyolefin microporous membrane.

[0193] The substrate preferably contains a plasticizer. When the substrate contains a plasticizer, the bonding force between the substrate and the covering layer is improved, and it is easier to control the 180° peel strength to be more than 200gf / cm. The amount of the plasticizer is based on the total mass of the substrate, preferably 0.1 parts by mass or more and 1.6 parts by mass or less, more preferably 0.2 parts by mass or more and 1.2 parts by mass or less, and further preferably 0.3 parts by mass or more and 1.0 parts by mass or less. By making the amount of the plasticizer within the above range, the internal resistance of the battery can be reduced and the bonding force between the substrate and the covering layer can be increased. As a plasticizer, for example, hydrocarbons such as liquid paraffin, esters such as dioctyl phthalate and dibutyl phthalate; higher alcohols such as oleyl alcohol and stearyl alcohol, etc. can be listed. Among these, the plasticizer is preferably liquid paraffin.

[0194] The porosity of the substrate is preferably 30% to 65%, more preferably 35% to 60%. It is further preferably 35% to 50%, or 40% to 50%. As a result, the coating layer is appropriately infiltrated into the micropores of the substrate, making it easier to control the 180° peel strength to be above 200 gf / cm. The porosity is determined by the volume (cm) of the sample of the substrate. 3 ), mass (g), film density (g / cm 3 ), is obtained by the following formula:

[0195] Porosity (%) = (volume - mass / membrane density) / volume × 100

[0196] Here, for example, in the case of a polyolefin microporous membrane formed of polyethylene, the membrane density can be assumed to be 0.95 g / cm 3 The porosity can be adjusted by changing the stretching ratio of the polyolefin microporous membrane.

[0197] The air permeability of the substrate is preferably 10 seconds / 100 cm 3 Above and 450 seconds / 100cm 3 Less than 40 seconds / 100 cm 3 More than 300 seconds / 100cm 3Below, more preferably 50 seconds / 100cm 3 Above and 250 seconds / 100cm 3 Below, particularly preferably 60 seconds / 100 cm 3 More than 200 seconds / 100cm 3 Alternatively, it can be 60 seconds / 100 cm 3 More than 150 seconds / 100cm 3 As a result, the coating layer is appropriately impregnated into the micropores of the substrate, making it easier to control the 180° peel strength to be above 200 gf / cm. The air permeability is the air permeability resistance measured in accordance with JIS P-8117. The air permeability can be adjusted by changing the stretching temperature and / or stretching ratio of the substrate.

[0198] The average pore size of the substrate is preferably 0.15 μm or less, more preferably 0.10 μm or less, and preferably 0.01 μm or more. From the viewpoint of suppressing the self-discharge of the storage device and suppressing the reduction of capacity, it is appropriate to set the average pore size to 0.15 μm or less. From the viewpoint of improving compactness, it is preferably 0.08 μm or less. The average pore size can be adjusted by changing the stretching ratio when manufacturing the substrate, etc.

[0199] The puncture strength of the substrate is preferably 200 gf or more, more preferably 300 gf or more, further preferably 400 gf or more, preferably 2,000 gf or less, more preferably 1,000 gf or less. From the viewpoint of suppressing film damage caused by detached active materials when the separator is wound together with the electrode, and from the viewpoint of suppressing the risk of short circuit caused by electrode expansion and contraction associated with charging and discharging, the puncture strength is also preferably 200 gf or more. On the other hand, from the viewpoint of being able to reduce the width shrinkage caused by orientation relaxation during heating, the puncture strength is preferably 2,000 gf or less. The puncture strength is measured according to the method described in the embodiment. The puncture strength can be adjusted by adjusting the stretching ratio and / or stretching temperature of the substrate.

[0200] The type, molecular weight and composition of the polyolefin resin constituting the polyolefin microporous membrane can be adjusted, for example, by controlling the type, molecular weight and blending ratio of high molecular raw materials such as polyolefins in the manufacturing process of the polyolefin microporous membrane. In addition, for a multilayer polyolefin resin microporous membrane having a structure in which two or more layers of polyolefin resin microporous membranes of the same or different types are stacked, it can also be adjusted as described above.

[0201] The polyolefin microporous membrane has a porous structure in which a large number of very small pores are aggregated to form dense interconnected pores. Therefore, the polyolefin microporous membrane has extremely excellent ion permeability and high strength in a state containing an electrolyte.

[0202] The thickness of the substrate (hereinafter referred to as the substrate film thickness) is preferably 2 μm or more, more preferably 5 μm or more, further preferably 6 μm or more, particularly preferably 7 μm or more, preferably 100 μm or less, more preferably 60 μm or less, further preferably 50 μm or less, particularly preferably 16 μm or less. From the viewpoint of improving mechanical strength, it is preferred to set the substrate film thickness to 2 μm or more. On the other hand, when the substrate film thickness is set to 100 μm or less, the volume occupied by the separator in the storage device is reduced, and therefore, there is a tendency to become advantageous in terms of the high capacity of the storage device, so it is preferred.

[0203] 〈Covering layer〉

[0204] The separator for storage device of the present embodiment includes a covering layer, and the covering layer is arranged on at least one surface of the substrate. That is, the covering layer can be arranged only on one side of the substrate, or it can also be arranged on both sides. "Arranged on the surface" means: it can be arranged on the entire surface of the substrate, or it can also be arranged locally. The covering layer is intended to be directly bonded to the electrode. It is preferably arranged in a manner that the substrate and the electrode are bonded with the covering layer sandwiched therebetween, so that the covering layer is directly bonded to the electrode. The covering layer is preferably a coating layer formed by a method of applying a coating liquid containing an inorganic filler and a granular polymer to the substrate.

[0205] The covering layer comprises an inorganic filler and a granular polymer of a thermoplastic polymer. The covering layer may further comprise a resin binder, a water-soluble polymer, and other additives. The covering layer may have at least two Tgs based on the Tg of the granular polymer composed of the thermoplastic polymer and the Tg of the thermoplastic polymer as the binder.

[0206] (Inorganic filler)

[0207] As the inorganic filler, it is preferred to have a melting point of 200°C or above or a thermal decomposition temperature of 200°C or above, a high electrical insulation, and an electrochemically stable filler within the use range of power storage devices such as lithium ion secondary batteries. As such inorganic fillers, for example, inorganic oxides (oxide-based ceramics) such as aluminum oxide, silicon dioxide, titanium oxide, zirconium oxide, magnesium oxide, cerium oxide, yttrium oxide, zinc oxide, and iron oxide; inorganic nitrides (nitride-based ceramics) such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, barium sulfate, aluminum hydroxide, aluminum hydroxide, potassium titanate, talc, kaolinite, dickite, pearl clay, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These can be used alone or in combination of two or more. Among these, the inorganic filler is preferably at least one selected from the group consisting of alumina, barium sulfate, and aluminum hydroxide (boehmite).

[0208] The lower limit of the average particle size of the inorganic filler is preferably 50 nm or more, 100 nm or more, 150 nm or more, 200 nm or more, 250 nm or more, 300 nm or more, 350 nm or more, or 400 nm or more, and the upper limit is preferably 2000 nm or less, 1100 nm or less, 800 nm or less, 450 nm or less, 400 nm or less, 350 nm or less, or 300 nm or less.

[0209] From the viewpoint of maintaining the voids for ion permeation through the covering layer and improving the rate characteristics, the average particle size of the inorganic filler is preferably 50nm or more. From the viewpoint of improving the filling rate of the inorganic filler in the covering layer and improving the heat shrinkage resistance, the average particle size of the inorganic filler is preferably 2000nm or less. The average particle size of the inorganic filler is preferably, for example, 180nm or more and 300nm or less. The reason is that, especially when the thickness of the covering layer is small, a uniform covering layer thickness is formed, and the heat shrinkage resistance is improved. The average particle size of the inorganic filler is preferably, for example, 150nm or more and 500nm or less, or 200nm or more and 450nm or less. The reason is that it is possible to highly take into account the rate characteristics and heat shrinkage resistance. The "average particle size" of the inorganic filler is measured using the method described in the embodiment. As a method for adjusting the particle size and distribution of the inorganic filler, for example, a method of reducing the particle size by crushing the inorganic filler using a suitable pulverizing device such as a ball mill, a bead mill, a jet mill, etc. can be cited. With regard to the particle size distribution of the inorganic filler, in a graph of frequency relative to particle size, the peak can be made one. However, it is also possible to make the peaks two or to form a trapezoidal spectrogram that does not form a peak. As the coefficient of variation of the particle size distribution of the inorganic filler, it is preferably 0.55 or less, more preferably 0.50 or less, and further preferably 0.45 or less. From the viewpoint of suppressing deformation at a temperature exceeding the melting point of the substrate, and improving the inclination rate of the covering layer, and the viewpoint of improving the bonding force with the electrode, it is preferred to make the coefficient of variation of the particle size distribution be 0.55 or less.

[0210] As the shape of the inorganic filler, for example, plate-like, flaky, needle-like, columnar, spherical, polyhedral and block-like can be listed. A variety of inorganic fillers having these shapes can be used in combination. From the viewpoint of increasing the inclination rate of the covering layer and improving the adhesion to the electrode, the block-like shape is preferred.

[0211] The aspect ratio of the inorganic filler is preferably 1.0 or more and 2.5 or less, more preferably 1.1 or more and 2.0 or less. From the viewpoint of suppressing the moisture adsorption of the separator, suppressing the capacity degradation during repeated cycles, suppressing the deformation at a temperature exceeding the melting point of the substrate, and improving the inclination of the covering layer and the adhesion to the electrode, the aspect ratio is preferably 2.5 or less. It is believed that the reason for increasing the inclination by making the aspect ratio of the inorganic filler 1.0 or more and 2.5 or less is that the particle orientation in the covering layer is small, so it is easy to form a stacked structure.

[0212] The particle size distribution of the inorganic filler obtained by dividing the standard deviation SD value of the volume average particle diameter of the inorganic filler by the D50 value is preferably below 0.55, more preferably below 0.50, and further preferably below 0.45. From the viewpoint of suppressing the deformation at a temperature exceeding the melting point of the substrate and improving the inclination rate of the covering layer, and the viewpoint of improving the bonding force of the electrode, it is preferred that the particle size distribution is below 0.55. It is believed that the reason for increasing the inclination rate by making the particle size distribution of the inorganic filler be below 0.55 is that the uniformity of the particles becomes higher, the contact rate between the particles improves, thereby easily forming a stacked structure.

[0213] The amount of the inorganic filler is, for example, 20 to 100 parts by mass, 30 to 80 parts by mass, 35 to 70 parts by mass, or 40 to 60 parts by mass, based on the total mass of the covering layer.

[0214] (Granular polymer)

[0215] The granular polymer is a particle of a thermoplastic polymer. From the viewpoint of improving the adhesion between the separator and the electrode, the granular polymer preferably contains a thermoplastic polymer having a glass transition temperature or a melting point of 20°C or more and 200°C or less. The glass transition temperature refers to the midpoint glass transition temperature described in JIS K7121, which is determined according to the DSC curve obtained by differential scanning calorimetry (DSC). Specifically, the temperature at the intersection of the following straight line and the curve can be used as the glass transition temperature, the straight line being a straight line obtained by extending the low temperature side baseline in the DSC curve to the high temperature side and a straight line obtained by extending the high temperature side baseline in the DSC curve to the low temperature side in the longitudinal direction, and the curve being a curve of the step-shaped change portion of the glass transition. In more detail, it can be determined according to the method described in the embodiment.

[0216] In addition, "glass transition" refers to the heat flow change that occurs on the heat-absorbing side in DSC, which is accompanied by a change in the state of the polymer as a test piece. This heat flow change is observed in the form of a step-like change in the DSC curve. "Step-like change" means: in the DSC curve, the part where the curve leaves the low-temperature side baseline so far and moves to the new high-temperature side baseline. It should be noted that the part composed of step-like changes and peaks is also included in the step-like change.

[0217] In addition, in the step-shaped change portion, when the upper side is set as the heat dissipation side, it can also be expressed as a point where the upward convex curve changes to a downward convex curve.

[0218] The "peak" refers to the portion of the DSC curve from when the curve leaves the low temperature side baseline until it returns to the same baseline. The "baseline" refers to the DSC curve at a temperature region where the test piece does not undergo phase change or reaction.

[0219] The glass transition temperature (Tg) of the particulate polymer is preferably 10°C or more and 110°C or less, more preferably 45°C or more, further preferably 80°C or more, and further preferably 90°C or more. From the viewpoint of improving the adhesive force after electrolyte injection and improving the blocking resistance, it is particularly preferably higher than 90°C. From the viewpoint of being able to maintain a stable shape at a higher temperature, it can be 92°C or more.

[0220] The Tg of the particulate polymer is preferably 10° C. or higher from the viewpoint of suppressing adhesion (blocking) of separators adjacent to each other via the covering layer during storage and transportation of the electrical storage device separator and in the manufacturing process of the electrical storage device.

[0221] On the other hand, from the viewpoint of obtaining good adhesion to the electrode, the Tg of the granular polymer is preferably 110°C or less. The Tg of the granular polymer can be appropriately adjusted, for example, by changing the type of monomer used in the manufacture of the granular polymer and the blending ratio of each monomer when the granular polymer is a copolymer. That is, for each monomer used in the manufacture of the granular polymer, the glass transition temperature can be estimated based on the Tg of its homopolymer generally shown (for example, recorded in "Polymer Handbook" (A WILEY-INTERSCIENCE PUBLICATION)) and the blending ratio of the monomer. For example, the Tg of a copolymer in which monomers such as methyl methacrylate, acrylonitrile and methacrylic acid that provide a homopolymer of about 100°C are copolymerized at a high ratio becomes higher, and the Tg of a copolymer in which monomers such as n-butyl acrylate and 2-ethylhexyl acrylate that provide a homopolymer of about -50°C are copolymerized at a high ratio becomes lower. In addition, the Tg of the copolymer can also be estimated using the FOX formula shown below.

[0222] 1 / Tg=W1 / Tg1+W2 / Tg2+···+W i / Tg i +···W n / Tg n (1)

[0223] Here, in the formula, Tg(K) is the Tg of the copolymer, Tg i (K) is the Tg of the homopolymer of monomer i, W i is the mass fraction of each monomer. i is an integer of 1 to n, and n is the number of types of monomers constituting the copolymer. However, as the glass transition temperature Tg of the particulate polymer in the present embodiment, the value measured by the method using the above-mentioned DSC is adopted.

[0224] From the viewpoint of adhesion between the separator and the electrode and preventing the granular polymer from falling off the covering layer, the average particle size of the granular polymer is preferably 0.5 times or more and 5 times or less, more preferably 1 times or more and 2 times or less, further preferably 1.1 times or more and less than 1.5 times, and particularly preferably 1.2 times or more and 1.4 times or less relative to the thickness of the covering layer. In the present application, the "average particle size" of the granular polymer refers to the volume average particle size (D50) measured by the measurement method described in the examples.

[0225] The "primary particles" of the particulate polymer refer to independent particles that are integrated by covalent bonds. On the other hand, the form in which two or more primary particles are in contact and form an aggregate is called a "secondary particle".

[0226] The particle size distribution MV / MN of the granular polymer obtained by dividing the volume average particle size MV of the granular polymer by the number average particle size MN is preferably less than 1.1, more preferably less than 1.10, and further preferably less than 1.05. From the perspectives of ensuring the thickness uniformity of the covering layer, improving the cycle characteristics, improving the adhesion to the electrode, reducing the amount of the granular polymer on the small particle size side buried in the covering layer, improving the adhesion to the electrode, improving the heat resistance, and reducing the total thickness of the separator, the particle size distribution of the granular polymer is preferably within the above range. The lower limit of the particle size distribution MV / MN of the granular polymer is not particularly limited and may be greater than 1.01 or 1.01.

[0227] The granular polymer contained in the covering layer is preferably in the form of primary particles. The average particle size of the primary particles of the granular polymer is preferably 1 μm or more and 10 μm or less, more preferably 1 μm or more and 5 μm or less, and further preferably 2 μm or more and 5 μm or less. The granular polymer is in the form of primary particles means that the granular polymer is uniformly dispersed in the covering layer, thereby improving the 180° peel strength, improving the adhesion to the electrode, suppressing thermal shrinkage, and ensuring the thickness uniformity of the covering layer. If the average particle size of the primary particles is 1 μm or more and 10 μm or less, it is easy to form a structure in which the granular polymer protrudes from the surface of the covering layer, improving the adhesion to the electrode, and suppressing thermal shrinkage.

[0228] Examples of the thermoplastic polymer include (meth)acrylic polymers, conjugated diene polymers, polyvinyl alcohol resins, and fluorine-containing resins.

[0229] From the viewpoint of high adhesion to the electrode and low thermal shrinkage, the thermoplastic polymer more preferably includes a (meth)acrylic polymer. "(Meth)acrylic polymer" refers to a polymer or copolymer containing a (meth)acrylic compound as a monomer. The (meth)acrylic compound can be represented by the following general formula.

[0230] CH2=CR Y1 -COO-R Y2

[0231] In the formula, R Y1 Represents a hydrogen atom or a methyl group; R Y2 represents a hydrogen atom or a monovalent hydrocarbon group. Y2 In the case of a monovalent hydrocarbon group, it may have a substituent and may have a heteroatom. Examples of the monovalent hydrocarbon group include: a linear alkyl group, a cycloalkyl group, and an aryl group, which may be straight or branched. Examples of the substituent include a hydroxyl group and a phenyl group, and examples of the heteroatom include a halogen atom and an oxygen atom. One (meth)acrylic acid compound may be used alone or two or more (meth)acrylic acid compounds may be used in combination. Examples of the (meth)acrylic acid compound include (meth)acrylic acid, linear alkyl (meth)acrylates, cycloalkyl (meth)acrylates, (meth)acrylates having a hydroxyl group, and aryl (meth)acrylates.

[0232] More specifically, examples of the chain alkyl (meth)acrylate include chain alkyl groups having 1 to 3 carbon atoms, such as methyl, ethyl, n-propyl, and isopropyl; n-butyl, isobutyl, tert-butyl, n-hexyl, 2-ethylhexyl; and chain alkyl groups having 4 or more carbon atoms, such as lauryl. Examples of the aryl (meth)acrylate include phenyl (meth)acrylate.

[0233] Specific examples of the (meth)acrylate include (meth)acrylates having a chain alkyl group such as methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, butyl acrylate, isobutyl acrylate, tert-butyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, lauryl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, isobutyl methacrylate, tert-butyl methacrylate, n-hexyl methacrylate, 2-ethylhexyl methacrylate, and lauryl methacrylate; and (meth)acrylates having an aromatic ring such as phenyl (meth)acrylate and benzyl (meth)acrylate.

[0234] Conjugated diene polymers are polymers having conjugated diene compounds as monomer units, which are easily compatible with electrodes, so they are preferred. As conjugated diene compounds, for example, 1,3-butadiene, 2-methyl-1,3-butadiene, 2,3-dimethyl-1,3-butadiene, 2-chloro-1,3-butadiene, substituted straight-chain conjugated pentadienes, substituted and side-chain conjugated hexadienes can be listed, and they can be used alone or in combination of two or more. Among these, 1,3-butadiene is particularly preferred. Conjugated diene polymers can contain (meth) acrylic acid compounds or other monomers described later as monomer units. As such monomers, for example, styrene-butadiene copolymers and their hydrides, acrylonitrile-butadiene copolymers and their hydrides, acrylonitrile-butadiene-styrene copolymers and their hydrides can be listed.

[0235] Examples of the polyvinyl alcohol-based resin include polyvinyl alcohol and polyvinyl acetate.

[0236] From the viewpoint of voltage resistance, fluorine-containing resins are preferred, and examples thereof include polyvinylidene fluoride, polytetrafluoroethylene, and copolymers containing fluorine atoms, such as vinylidene fluoride-hexafluoropropylene copolymers, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, and ethylene-tetrafluoroethylene copolymers. The fluorine-containing resin is preferably a copolymer containing fluorine atoms.

[0237] Among the thermoplastic polymers listed above, the granular polymer preferably contains at least one selected from the group consisting of a copolymer containing (meth)acrylate as a monomer, a styrene-butadiene copolymer, and a copolymer containing fluorine atoms. Regarding the copolymer containing (meth)acrylate as a monomer, it is more preferred to contain a copolymer containing (meth)acrylic acid, butyl (meth)acrylate, and ethylhexyl (meth)acrylate as monomers. By making the granular polymer contain these specific thermoplastic polymers, it is possible to provide a separator for a storage device with higher adhesion to the electrode and lower thermal shrinkage.

[0238] The particulate polymer preferably includes a crosslinking monomer. As the crosslinking monomer, there is no particular limitation, and examples thereof include monomers having two or more free radical polymerizable double bonds, monomers having a functional group that provides a self-crosslinking structure during or after polymerization, etc. These can be used alone or in combination of two or more.

[0239] As a monomer having two or more free radical polymerizable double bonds, for example, divinylbenzene and multifunctional (meth) acrylates can be listed, preferably multifunctional (meth) acrylates. Multifunctional (meth) acrylates can be at least one selected from the group consisting of difunctional (meth) acrylates, trifunctional (meth) acrylates and tetrafunctional (meth) acrylates. Specifically, for example, polyoxyethylene diacrylate, polyoxyethylene dimethacrylate, polyoxypropylene diacrylate, polyoxypropylene dimethacrylate, neopentyl glycol diacrylate, neopentyl glycol dimethacrylate, butanediol diacrylate, butanediol dimethacrylate, trimethylolpropane triacrylate, trimethylolpropane trimethacrylate, pentaerythritol tetraacrylate and pentaerythritol tetramethacrylate can be listed. They can be used alone or in combination of two or more. Among them, from the same viewpoint as above, it is preferably at least one of trimethylolpropane triacrylate or trimethylolpropane trimethacrylate.

[0240] (resin binder)

[0241] The covering layer preferably includes a resin binder for bonding the inorganic fillers to each other and to the substrate. The type of resin used as the resin binder is not particularly limited, and a resin that is insoluble in the electrolyte of a storage device such as a lithium ion secondary battery and is electrochemically stable within the use range of the storage device such as a lithium ion secondary battery can be used.

[0242] Specific examples of the resin as the resin binder include polyolefins such as polyethylene and polypropylene; fluorine-containing resins such as polyvinylidene fluoride and polytetrafluoroethylene; fluorine-containing rubbers such as vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer and ethylene-tetrafluoroethylene copolymer; rubbers such as styrene-butadiene copolymer and its hydrogenated product, acrylonitrile-butadiene copolymer and its hydrogenated product, acrylonitrile-butadiene-styrene copolymer and its hydrogenated product, methacrylate-acrylate copolymer, styrene-acrylate copolymer, acrylonitrile-acrylate copolymer, ethylene-propylene rubber, polyvinyl alcohol, polyvinyl acetate, etc.; cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, carboxymethyl cellulose, etc.; and resins having a melting point of 180° C. or above such as polyphenylene ether, polysulfone, polyether sulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester; or resins having no melting point but a decomposition temperature of 200° C. or above. These may be used alone or in combination of two or more.

[0243] The resin binder may include, for example, a resin latex binder. As the resin latex binder, for example, a copolymer of an unsaturated carboxylic acid monomer and other monomers copolymerizable therewith may be used. Here, as aliphatic conjugated diene monomers, for example, butadiene and isoprene may be cited, as unsaturated carboxylic acid monomers, for example, (meth)acrylic acid may be cited, and as other monomers, for example, styrene may be cited. The polymerization method of such a copolymer is not particularly limited, and emulsion polymerization is preferred. As the method for emulsion polymerization, there is no particular limitation, and known methods may be used. There is no particular limitation on the method for adding the monomers and other components, and a method of adding all at once, a method of adding in batches, and a method of adding continuously may all be adopted. As for the polymerization method, one-stage polymerization, two-stage polymerization, or multi-stage polymerization of three or more stages may all be adopted.

[0244] Specific examples of the resin binder include the following (1) to (7).

[0245] (1) Polyolefins, such as polyethylene, polypropylene, ethylene-propylene rubber and their modifications;

[0246] (2) Conjugated diene polymers, such as styrene-butadiene copolymers and their hydrogenates, acrylonitrile-butadiene copolymers and their hydrogenates, acrylonitrile-butadiene-styrene copolymers and their hydrogenates;

[0247] (3) acrylic polymers, such as methacrylate-acrylate copolymers, styrene-acrylate copolymers, and acrylonitrile-acrylate copolymers;

[0248] (4) Polyvinyl alcohol-based resins, such as polyvinyl alcohol and polyvinyl acetate;

[0249] (5) Fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers and ethylene-tetrafluoroethylene copolymers;

[0250] (6) Cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose and carboxymethyl cellulose; and

[0251] (7) Resins having a melting point and / or glass transition temperature of 180°C or higher, or polymers having no melting point but a decomposition temperature of 200°C or higher, such as polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide and polyester.

[0252] When the resin binder is a resin latex binder, its volume average particle diameter (D50) can be, for example, 50 nm or more and 500 nm or less, 60 nm or more and 460 nm or less, or 80 nm or more and 250 nm or less. The volume average particle diameter of the resin binder can be controlled by adjusting the polymerization time, polymerization temperature, raw material composition ratio, raw material input sequence, pH, etc.

[0253] From the viewpoint of improving 180° peel strength, the glass transition temperature of the resin binder is preferably 25° C. or lower, more preferably 10° C. or lower, and further preferably -15° C. or lower. From the viewpoint of permeability, the glass transition temperature of the resin binder is preferably -60° C. or higher.

[0254] From the viewpoint of improving the 180° peel strength, the volume average particle size (D50) of the resin binder is preferably more than 1 times the average pore size of the polyolefin microporous membrane, more preferably more than 2 times, and further preferably more than 2.5 times. By selecting the volume average particle size (D50) of the resin binder in this way, the resin binder can be maintained on the surface of the polyolefin microporous membrane, and the 180° peel strength is improved. From the viewpoint of improving the rate characteristics, the volume average particle size (D50) of the resin binder is preferably less than 10 times the average pore size of the polyolefin microporous membrane. From the viewpoint of maintaining the permeability at a low level and inhibiting adhesion, the content ratio of the resin binder in the covering layer relative to the total amount of the covering layer can, for example, exceed 0 mass parts and be less than 50 mass parts, more than 1 mass part and less than 20 mass parts, more than 2 mass parts and less than 10 mass parts, or more than 3 mass parts and less than 5 mass parts.

[0255] From the viewpoints of wettability to the substrate, adhesion between the substrate and the granular polymer, adhesion between the covering layer and the granular polymer, adhesion between the substrate and the covering layer, and adhesion to the electrode, the Tg of the resin binder is preferably lower than 40°C. From the viewpoint of ion permeability, the Tg of the resin binder is more preferably -100°C or higher, further preferably -50°C or higher, and particularly preferably -40°C or higher. From the viewpoint of adhesion between the substrate and the granular polymer, the Tg is more preferably lower than 20°C, further preferably lower than 15°C, and particularly preferably lower than 0°C.

[0256] (Water-soluble polymer)

[0257] The covering layer may further contain a water-soluble polymer in addition to the granular polymer containing an inorganic filler and a thermoplastic polymer. The water-soluble polymer may be incompatible with the thermoplastic polymer constituting the granular polymer. Generally speaking, the water-soluble polymer functions as a dispersant in the coating liquid used to form the covering layer of the granular polymer containing an inorganic filler and a thermoplastic polymer, and functions as a dispersant and / or a water retaining agent when the coating liquid is a water-based coating.

[0258] The content of the water-soluble polymer in the covering layer is preferably 0.04 mass parts or more and 5 mass parts or less relative to 100 mass parts of inorganic filler, more preferably 0.04 mass parts or more and 1.5 mass parts or less, and further preferably 0.1 mass parts or more and 1 mass parts or less. By making the content of the water-soluble polymer in the covering layer more than 0.04 mass parts, the bonding property of the inorganic components is improved, and thermal shrinkage can be further suppressed. In addition, the component sedimentation when making the slurry of the covering layer can be suppressed, and it can be stably dispersed. By making the content of the water-soluble polymer in the covering layer less than 5 mass parts, the stripes and unevenness when forming the covering layer can be suppressed.

[0259] The water-soluble polymer also contributes to the bonding between the inorganic fillers in the coating layer. From the viewpoint of suppressing thermal shrinkage of the separator, the water-soluble polymer preferably has a weight loss rate of less than 10% at 150°C when the weight at 50°C in thermogravimetric measurement is 100%.

[0260] The water-soluble polymer may be a polymer derived from natural materials, a synthetic product, a semi-synthetic product, etc. From the viewpoint of coating of inorganic and organic components, especially water-based coating, anionic, cationic, amphoteric or nonionic polymers are preferred, and anionic, cationic or amphoteric polymers are more preferred.

[0261] Examples of the anionic polymer include modified starches such as carboxymethyl starch and starch phosphate; anionic cellulose derivatives such as carboxymethyl cellulose; ammonium salts or alkali metal salts of polyacrylic acid; gum arabic; carrageenan; sodium chondroitin sulfate; sulfonic acid compounds such as sodium polystyrene sulfonate, sodium polyisobutylene sulfonate and naphthalenesulfonic acid condensate salts; and polyethyleneimine xanthate.

[0262] Among these, from the viewpoint of obtaining an appropriate balance among rigidity, rate characteristics and cycle characteristics of the storage device, anionic polymers containing metal salts as counter cations are preferred, anionic cellulose derivatives, and ammonium salts or alkali metal salts of polyacrylic acid are also preferred, and from the viewpoint of a balance between heat resistance and rate characteristics, alkali metal salts of polyacrylic acid are further preferred, and sodium polyacrylate is still more preferred.

[0263] The ammonium salt or alkali metal salt of polyacrylic acid refers to: -COO derived from multiple carboxylic acid groups - A polymer in which at least one of the moieties forms a salt with an ammonium ion or an alkali metal ion. Examples of the alkali metal ion include sodium ions (Na + ), potassium ion (K + )wait.

[0264] The ammonium salt or alkali metal salt of polyacrylic acid may be at least one of the following (I) to (III):

[0265] (I) A monomer having an ammonium salt or an alkali metal salt of a carboxylic acid (C i ) homopolymer or multiple monomers (C i ) and other monomers;

[0266] (II) A monomer having an ammonium salt or an alkali metal salt of a plurality of carboxylic acids (C ii ) homopolymer or monomer (C ii ) and other monomers; and

[0267] (III) Ammonium salts or alkali metal salts of polymers or copolymers obtained by polymerizing or copolymerizing monomers having a single or multiple carboxylic acids.

[0268] As a monomer having an ammonium salt or an alkali metal salt of a carboxylic acid (C i ), for example, sodium (meth)acrylate and ammonium (meth)acrylate can be mentioned.

[0269] As a monomer having an ammonium salt or an alkali metal salt of multiple carboxylic acids (C ii ), for example, ammonium salts or sodium salts of 11-(methacryloyloxy)undecane-1,1-dicarboxylic acid; ammonium salts, monosodium salts or disodium salts of ethylenically unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid and citraconic acid; and alicyclic polycarboxylic acids having a (meth)acryloyl group.

[0270] As a monomer (C i ) or monomer (C ii ) can be copolymerized with (meth)acrylamide; ethylenically unsaturated dicarboxylic acids such as fumaric acid, maleic acid, itaconic acid and citraconic acid; and ethylenically unsaturated dicarboxylic anhydrides such as maleic anhydride, itaconic anhydride and citraconic anhydride.

[0271] Examples of ammonium salts or alkali metal salts of polymers or copolymers obtained by polymerizing or copolymerizing monomers having a single or multiple carboxylic acids include sodium polyacrylate and ammonium polyacrylate.

[0272] The structures of the ammonium salt or alkali metal salt of polyacrylic acid described in (I) to (III) above may be repeated. It is desirable that when the ammonium salt or alkali metal salt of polyacrylic acid described in (I) to (III) above is dissolved in water, the content of polyvalent cations is small. Examples of polyvalent cations include magnesium ions, calcium ions, and iron ions. By reducing the content of these ions, the dispersibility of the granular polymer in the mixed slurry with the granular polymer is stabilized.

[0273] Examples of cationic polymers include cationic starch; chitosan; gelatin; homopolymers or copolymers of dimethylaminoethyl (meth)acrylate quaternary salt; homopolymers or copolymers of dimethylallylammonium chloride; polyamidine and copolymers thereof; polyvinyl imidazoline; dicyandiamide condensates; epichlorohydrin-dimethylamine condensates; and polyethyleneimine.

[0274] Examples of the amphoteric polymer include a (meth)acrylate dimethylaminoethyl quaternary salt-acrylic acid copolymer and a Hofmann degradation product of polyacrylamide.

[0275] Examples of nonionic polymers include starch and its derivatives; cellulose derivatives such as methyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose, and their ammonium salts or alkali metal salts; rubbers such as guar gum and their modified forms; and synthetic polymers such as polyvinyl alcohol, polyacrylamide, polyethylene glycol, polymethyl vinyl ether, polyisopropylacrylamide, and copolymers of vinyl alcohol and other monomers, and their modified forms.

[0276] The water-soluble polymer may or may not have a cyclic structure containing an amide bond. The water-soluble polymer having a cyclic structure containing an amide bond refers to a homopolymer or copolymer comprising a group having a cyclic structure containing an amide bond and a skeleton derived from a polymerizable double bond. The water-soluble polymer having a cyclic structure containing an amide bond may have a single or multiple cyclic structures containing an amide bond.

[0277] Examples of the group having a cyclic structure containing an amide bond include a group represented by the following formula (2).

[0278]

[0279] Specific examples of water-soluble polymers having a cyclic structure containing an amide bond include: homopolymers of N-vinylcaprolactam, i.e., poly(N-vinylcaprolactam), homopolymers of vinylpyrrolidone, i.e., polyvinylpyrrolidone (PVP), and the like, which contain a group having a cyclic structure containing an amide bond and a polymerizable double bond; copolymers containing two or more monomers (N-vinylcaprolactam, vinylpyrrolidone, etc.) having a group having a cyclic structure containing an amide bond and a polymerizable double bond; and copolymers formed by one or more monomers (N-vinylcaprolactam, vinylpyrrolidone, etc.) containing a group having a cyclic structure containing an amide bond and a polymerizable double bond and one or more other monomers having a polymerizable double bond (monomers other than monomers containing a group having a cyclic structure containing an amide bond and a polymerizable double bond).

[0280] Examples of monomers copolymerizable with a monomer containing a group having a cyclic structure containing an amide bond and a polymerizable double bond include: vinyl non-cyclic amides; (meth)acrylic acid and its esters; (meth)acrylamide and its derivatives; styrene and its derivatives; vinyl esters such as vinyl acetate; α-olefins; basic unsaturated compounds such as vinylimidazole and vinylpyridine and their derivatives; unsaturated compounds containing a carboxyl group and their anhydrides; vinyl sulfonic acid and its derivatives; vinyl ethylene carbonate and its derivatives; and vinyl ethers.

[0281] (additive)

[0282] The covering layer may be formed only of an inorganic filler, a granular polymer of a thermoplastic polymer, and an optional water-soluble polymer, or may further contain additives other than these. Examples of the additives include low molecular weight dispersants other than water-soluble polymers; thickeners; defoamers; and pH adjusters such as ammonium hydroxide. Specific examples of low molecular weight dispersants include monomers (C ii ) and non-polymeric compounds having ammonium salts or alkali metal salts of multiple carboxylic acids (such as sodium alginate and sodium hyaluronate), etc.

[0283] As a specific example of the defoaming agent, a surfactant (acetylene-based surfactant) composed of an ethoxylate of acetylene glycol represented by the following formula (A) is preferably used.

[0284]

[0285] {In the formula, R 5 ~R 8 Each independently represents an alkyl group having 1 to 10 carbon atoms, n and m independently represent an integer greater than or equal to 0, and n+m=between 0 and 40.

[0286] Specific examples of the alkyl group having 1 to 10 carbon atoms may be any of linear, branched, and cyclic groups, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl.

[0287] Specific examples of the acetylene diol represented by formula (A) include 2,5,8,11-tetramethyl-6-dodecene-5,8-diol, 5,8-dimethyl-6-dodecene-5,8-diol, 2,4,7,9-tetramethyl-5-decene-4,7-diol, 4,7-dimethyl-5-decene-4,7-diol, 2,3,6,7-tetramethyl-4-octyne-3,6-diol, 3,6-dimethyl-4-octyne-3,6-diol, 2,5-dimethyl-3-hexyne-2,5-diol, ethoxylated products of 2,4,7,9-tetramethyl-5-decyne-4,7-diol (number of moles of ethylene oxide added: 1.3), 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2,4,7,9-tetramethyl-5-decyne-4,7-diol ethoxylated product (ethylene oxide addition mole number: 10), 2,4,7,9-tetramethyl-5-decyne-4,7-diol ethoxylated product (ethylene oxide addition mole number: 30) and 3,6-dimethyl-4-octyne-3,6-diol ethoxylated product (ethylene oxide addition mole number: 20). The defoaming agent may be used alone or in combination of two or more.

[0288] The acetylene-based surfactant can also be obtained as a commercial product. Examples of such commercial products include OLFINE SPC (manufactured by Nissin Chemical Industry Co., Ltd., 80 parts by mass of active ingredient, light yellow liquid), OLFINE AF-103 (manufactured by Nissin Chemical Industry Co., Ltd., light brown liquid), OLFINE AF-104 (manufactured by Nissin Chemical Industry Co., Ltd., light brown liquid), OLFINE SK-14 (manufactured by Nissin Chemical Industry Co., Ltd., light yellow viscous liquid), OLFINE AK-02 (manufactured by Nissin Chemical Industry Co., Ltd., light yellow viscous liquid), OLFINE AF-201F (manufactured by Nissin Chemical Industry Co., Ltd., light yellow viscous liquid), OLFINE D-10PG (manufactured by Nissin Chemical Industry Co., Ltd., 50 parts by mass of active ingredient, light yellow liquid), OLFINE E-1004 (manufactured by Nissin Chemical Industry Co., Ltd., 100 parts by mass of active ingredient, light yellow liquid), OLFINE OLFINE E-1010 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow liquid), OLFINE E-1020 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow liquid), OLFINE E-1030W (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 75 parts by mass, light yellow liquid), SURFYNOL 420 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow viscous body), SURFYNOL 440 (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 100 parts by mass, light yellow viscous body) and SURFYNOL 104E (manufactured by Nissin Chemical Industry Co., Ltd., active ingredient: 50 parts by mass, light yellow viscous body), etc.

[0289] As the surfactant of the additive, it is also possible to use a polyether surfactant and / or a silicone surfactant instead of or together with the acetylene surfactant. As a representative example of the polyether surfactant, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polyoxyethylene oleyl ether, polyoxyethylene stearyl ether, polyoxyethylene lauryl ether, polyoxyethylene dodecyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene octylphenyl ether, and polyoxyethylene-polyoxypropylene block copolymer can be listed. Among these, polyethylene glycol is particularly preferred. It should be noted that these surfactants can be used alone or in combination of two or more.

[0290] The polyether-based surfactant is also available as a commercial item. Examples of such commercial items include E-D052, E-D054, and E-F010 (manufactured by Sannopco).

[0291] As a silicone-based surfactant, as long as it contains at least a silicone chain, it can be any of linear, branched, and cyclic, and can contain any of a hydrophobic group and a hydrophilic group. Specific examples of hydrophobic groups include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, tert-butyl, n-pentyl, n-hexyl, n-heptyl, n-octyl, n-nonyl, and n-decyl; cyclic alkyl groups such as cyclohexyl; and aromatic hydrocarbon groups such as phenyl. Specific examples of hydrophilic groups include amino groups, thiol groups, hydroxyl groups, alkoxy groups, carboxylic acids, sulfonic acids, phosphoric acids, nitric acids, and their organic salts, inorganic salts, ester groups, aldehyde groups, glyceryl groups, and heterocyclic groups. Representative examples of silicone-based surfactants include dimethyl silicone, methylphenyl silicone, chlorophenyl silicone, alkyl-modified silicone, fluorine-modified silicone, amino-modified silicone, alcohol-modified silicone, phenol-modified silicone, carboxyl-modified silicone, epoxy-modified silicone, fatty acid ester-modified silicone, and polyether-modified silicone.

[0292] The silicone surfactant can also be obtained as a commercial product. Examples of such commercial products include BYK-300, BYK-301, BYK-302, BYK-306, BYK-307, BYK-310, BYK-313, BYK-320, BYK-333, BYK-341, BYK-345, BYK-346, BYK-347, BYK-348, and BYK-349 (these are trade names, manufactured by BYK-Chemie-Japan); KM-80, KF- 351A, KF-352A, KF-353, KF-354L, KF-355A, KF-615A, KF-945, KF-640, KF-642, KF-643, KF-6020, X-22-4515, KF-6011, KF-6012, KF-6015, KF-6017 (the above are trade names, manufactured by Shin-Etsu Chemical Co., Ltd.); SH-28PA, SH8400, SH-190, SF-8428 (the above are trade names, manufactured by Dow Corning Toray Co., Ltd.); Polyflow KL-245, Polyflow KL-270, Polyflow KL-100 (these are trade names, manufactured by Kyoeisha Chemical Co., Ltd.); SILFACE SAG002, SILFACE SAG005, and SILFACE SAG0085 (these are trade names, manufactured by Nissin Chemical Industry Co., Ltd.), and the like.

[0293] (Amount of covering layer)

[0294] The amount of the covering layer relative to the substrate, that is, the amount of the covering layer per unit area of ​​one surface of the substrate, is preferably 0.5 g / m by weight. 2More preferably 1.0 g / m 2 Above, preferably 0.15 cm by volume 3 / m 2 More preferably 0.30 cm 3 / m 2 The upper limit of the amount of the covering layer is preferably 10.0 g / m 2 Below, more preferably 7.0g / m 2 Below, 3.50cm by volume 3 / m 2 Below, more preferably 2.50cm 3 / m 2 From the viewpoint of improving the adhesion between the covering layer and the electrode and suppressing thermal shrinkage, the amount of the covering layer is preferably greater than the above lower limit. From the viewpoint of suppressing a decrease in ion permeability, the amount of the covering layer is preferably less than the above upper limit.

[0295] (Thickness of the covering layer)

[0296] The thickness of any one of the covering layers disposed on at least one side of the substrate (the thickness of the inorganic filler portion) is preferably 0.3 μm or more and 5.0 μm or less, more preferably 0.5 μm or more and 2.5 μm or less, and further preferably 0.7 μm or more and 1.3 μm or less. If the thickness of the covering layer is 0.3 μm or more, the thermal shrinkage rate can be further suppressed, and the bonding force between the electrode and the substrate can be easily made uniform, and as a result, the characteristics of the storage device can be improved.

[0297] If the thickness is 1.3 μm or less, it is preferable because a decrease in ion permeability can be suppressed and a thin-film electric storage device separator can be obtained. That is, an electric storage device with a large capacity per unit volume can be manufactured by reducing the thickness of the separator.

[0298] On the other hand, from the viewpoint of further suppressing heat shrinkage and preventing the particulate polymer from slipping off the covering layer, the thickness of the covering layer is preferably 1.6 μm or more, or 2.1 μm or more.

[0299] The thickness can be adjusted by, for example, changing the type or concentration of the particulate polymer in the coating solution applied to the substrate, the amount of the coating solution applied, the coating method, the coating conditions, etc. However, the method for adjusting the thickness of the covering layer is not limited to these.

[0300] Figure 1 Schematic diagram of the surface of the cover layer of the separator for the electrical storage device according to the present embodiment. Figure 1As schematically shown in FIG. 1 , an inorganic filler (1) and a particulate polymer (2) of a thermoplastic polymer protruding from the inorganic filler are present on the surface of the cover layer (10). Figure 1 In the process, the particulate polymer does not aggregate with other particulate polymers and exists in the state of primary particles.

[0301] Figure 2 for Figure 1 AA cross-sectional view of a separator for a power storage device. Figure 2 As schematically shown in FIG. 1 , the covering layer (20) is formed in an inclined shape in such a manner that the thickness increases continuously as the inorganic filler portion, which is 1.5D or more away from the volume center of each granular polymer in the horizontal direction (the surface direction of the covering layer), approaches the protruding granular polymer (2). The slope of the inclined covering layer is gentler as it is away from the protruding granular polymer, and steeper as it is close to the protruding granular polymer. The inorganic filler (1) exists along the contour of the granular polymer and covers a portion of the periphery of the protruding portion, and the vicinity of the center of the protruding portion is exposed on the surface of the covering layer.

[0302] 《Method for manufacturing separator for electric storage device》

[0303] <Method for producing substrate>

[0304] The method for manufacturing the substrate is not particularly limited, and a known manufacturing method can be used, for example, any one of a wet porosification method or a dry porosification method can be used. If examples based on the wet porosification method are listed, for example, in the case where the substrate is a polyolefin microporous membrane, the following examples can be listed: a method of melting and kneading a polyolefin resin composition and a plasticizer to form a sheet, and extracting the plasticizer after stretching according to the situation, thereby making it porous; a method of melting and kneading a polyolefin resin composition containing a polyolefin resin as a main component, extruding it at a high stretch ratio, and then exfoliating the polyolefin crystal interface by heat treatment and stretching, thereby making it porous; a method of melting and kneading a polyolefin resin composition and an inorganic filler material to form a sheet, and then exfoliating the interface between the polyolefin and the inorganic filler material by stretching, thereby making it porous; and a method of dissolving the polyolefin resin composition, immersing it in a poor solvent for polyolefin to solidify the polyolefin, and removing the solvent at the same time, thereby making it porous.

[0305] Methods for preparing the substrate include, for example: a chemical bonding method in which a fiber web is immersed in a binder and dried to bond the fibers; a thermal bonding method in which heat-fusible fibers are mixed into the fiber web to partially melt the fibers to bond the fibers; a needle punching method in which a fiber web is repeatedly pierced with a barbed needle to mechanically interweave the fibers; and a water interweaving method in which a high-pressure water jet is sprayed from a nozzle onto the fiber web through a mesh (silk screen) to interweave the fibers.

[0306] Hereinafter, as an example of a method for producing a polyolefin microporous membrane, a method of melt-kneading a polyolefin resin composition and a plasticizer to form the mixture into a sheet and then extracting the plasticizer will be described.

[0307] The polyolefin resin composition and the plasticizer are melt-kneaded. As a melt-kneading method, for example, a method of introducing a polyolefin resin and other additives as required into a resin mixing device such as an extruder, a kneader, a laboplasticsil, a mixing roll and a Banbury mixer, and mixing the resin component by heating and melting the plasticizer at an arbitrary ratio. At this time, it is preferred that: before the polyolefin resin, other additives and the plasticizer are put into the resin mixing device, they are mixed in advance in a prescribed ratio using a Henschel mixer or the like. It is more preferred that: only a part of the plasticizer is put into the pre-mixing, and the remaining plasticizer is side-fed into the resin mixing device and mixed.

[0308] As the plasticizer, a nonvolatile solvent that can form a uniform solution at a temperature not lower than the melting point of the polyolefin can be used.

[0309] Examples of the plasticizer include hydrocarbons such as liquid paraffin and paraffin wax; esters such as dioctyl phthalate and dibutyl phthalate; and higher alcohols such as oleyl alcohol and stearyl alcohol. Among these, liquid paraffin is preferred.

[0310] The ratio of the polyolefin resin composition to the plasticizer is not particularly limited as long as it is a range in which they can be uniformly melt-kneaded and formed into a sheet-like shape. For example, the mass fraction of the plasticizer in the composition comprising the polyolefin resin composition and the plasticizer is preferably 30 parts by mass or more and 80 parts by mass or less, more preferably 40 parts by mass or more and 70 parts by mass or less. By setting the mass fraction of the plasticizer to this range, it is preferred from the viewpoint of the melt tension during melt forming and the formation of a uniform and fine pore structure.

[0311] The molten kneaded product obtained by heating, melting and kneading as described above is formed into a sheet. As a method for manufacturing a sheet-like formed body, for example, a method of extruding the molten kneaded product into a sheet through a T die, etc., and cooling it to a temperature sufficiently lower than the crystallization temperature of the resin component to solidify it can be cited. As the heat conductor used in cooling and solidification, metal, water, air and plasticizer itself can be cited, and metal rollers are preferred because of their high thermal conductivity. In this case, when it is contacted with a metal roller, if the molten kneaded product is sandwiched between the rollers, the thermal conductivity is further improved, and the sheet is oriented, the film strength is increased, and the surface smoothness of the sheet is also improved, so it is more preferred. The die lip spacing when extruding into a sheet from a T die is preferably 400 μm or more and 3000 μm or less, and more preferably 500 μm or more and 2500 μm or less.

[0312] Preferably, the sheet-like formed body thus obtained is then stretched. As a stretching treatment, uniaxial stretching or biaxial stretching can be suitably used. From the viewpoints of the strength of the obtained microporous film, biaxial stretching is preferably used. If the sheet-like formed body is stretched at a high ratio along a biaxial direction, the molecules are oriented along the surface direction, and the porous substrate finally obtained is not easy to break and has high puncture strength. As a stretching method, for example, methods such as simultaneous biaxial stretching, successive biaxial stretching, multi-stage stretching and multiple stretching can be listed. From the viewpoints of the improvement of puncture strength, stretching uniformity, and closure, simultaneous biaxial stretching is preferably used.

[0313] The stretching ratio is based on the surface ratio, preferably in the range of 20 times or more and 100 times or less, more preferably in the range of 25 times or more and 50 times or less. The stretching ratio in each axial direction is preferably in the range of 4 times or more and 10 times or less in the MD direction, and in the range of 4 times or more and 10 times or less in the TD direction, and more preferably in the range of 5 times or more and 8 times or less in the MD direction, and in the range of 5 times or more and 8 times or less in the TD direction. By setting the stretching ratio to the ratio of this range, more sufficient strength can be given, and the film breakage in the stretching process can be prevented, and high productivity can be obtained, which is preferred from this aspect. It should be noted that the MD direction refers to the mechanical direction when, for example, a polyolefin microporous membrane is continuously formed, and the TD direction refers to the direction crossing the MD direction at an angle of 90 °.

[0314] The sheet-like formed body obtained as described above can be further calendered. Calendering can be implemented, for example, by a pressurization method using a double belt press or the like. By calendering, the orientation of the surface layer of the sheet-like formed body can be particularly increased. The calendering ratio is preferably greater than 1 times and less than 3 times, more preferably greater than 1 times and less than 2 times. By setting the calendering ratio to this range, the membrane strength of the porous substrate finally obtained is increased, and a more uniform porous structure can be formed in the thickness direction of the membrane, which is preferred from this aspect.

[0315] Next, the plasticizer is removed from the sheet-like formed body to obtain a porous substrate. As a method for removing the plasticizer, for example, a method of immersing the sheet-like formed body in an extraction solvent to extract the plasticizer and fully drying it can be cited. The method of extracting the plasticizer can be any of an intermittent method and a continuous method. In order to suppress the shrinkage of the porous substrate, it is preferred to restrain the ends of the sheet-like formed body in a series of steps of immersion and drying.

[0316] The removal of the plasticizer can be controlled in a manner such that the amount of the plasticizer is preferably 0.1 parts by mass or more and 1.6 parts by mass or less, more preferably 0.2 parts by mass or more and 1.2 parts by mass or less, or 0.3 parts by mass or more and 1.0 parts by mass or less, based on the total mass of the obtained substrate. By making the amount of the plasticizer within the above range, the internal resistance of the battery can be reduced and the bonding strength between the substrate and the covering layer can be increased.

[0317] As the extraction solvent, it is preferred to use a solvent that is a poor solvent for the polyolefin resin and a good solvent for the plasticizer, and has a boiling point lower than the melting point of the polyolefin resin. Examples of such extraction solvents include: hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane and 1,1,1-trichloroethane; non-chlorine halogenated solvents such as hydrofluoroethers and hydrofluorocarbons; alcohols such as ethanol and isopropanol; ethers such as diethyl ether and tetrahydrofuran; and ketones such as acetone and methyl ethyl ketone. It should be noted that these extraction solvents can be recovered and reused by operations such as distillation.

[0318] In order to suppress the shrinkage of the porous substrate, a heat treatment such as heat setting or heat relaxation may be performed after the stretching step or after the porous substrate is formed. The porous substrate may also be subjected to a post-treatment such as a hydrophilization treatment using a surfactant or the like, or a cross-linking treatment using ionizing radiation or the like.

[0319] An example of a dry porosification method different from the above-mentioned wet porosification method will be given.

[0320] First, without using a solvent, after melt kneading in an extruder, the film is directly stretched and oriented to make a film, and then, an annealing process, a cold stretching process and a hot stretching process are sequentially performed to make a microporous membrane. As a dry porous method, there can be listed: a method of stretching and oriented the molten resin from an extruder via a T die, and an inflation method, etc., and the method is not particularly limited.

[0321] 〈How to configure the cover layer〉

[0322] The coating layer is disposed on at least one surface of the substrate produced as described above. Examples of a method for disposing the coating layer include a method in which a coating liquid of a particulate polymer containing an inorganic filler and a thermoplastic polymer is applied to the substrate and then the medium described below is removed.

[0323] As the coating liquid, a dispersion obtained by dispersing an inorganic filler and a particulate polymer in a solvent or dispersion medium (hereinafter referred to as "medium") in which the particulate polymer is not dissolved can be used. Preferably, the particulate polymer can be synthesized by emulsion polymerization, and the emulsion obtained by the emulsion polymerization can be directly used as the coating liquid.

[0324] The medium of the coating liquid is preferably a medium that can uniformly and stably disperse or dissolve the inorganic filler, the particulate polymer and, if necessary, the water-soluble polymer, and examples thereof include N-methylpyrrolidone, N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, methanol, toluene, hot xylene, dichloromethane and hexane.

[0325] The medium of the coating liquid is preferably water or a mixed medium containing water and a water-soluble organic medium.

[0326] The water-soluble organic medium is not particularly limited, and examples thereof include ethanol and methanol, etc. Among these, water is more preferred.

[0327] When the coating liquid is applied to the substrate, if the coating liquid enters the interior of the substrate, the particulate polymer containing the polymer will block the surface and the interior of the pores of the substrate, and the permeability is likely to decrease. In this regard, in the case of an aqueous dispersion using water as the medium of the coating liquid, the coating liquid is difficult to enter the interior of the substrate, and the particulate polymer containing the polymer is likely to be mainly present on the outer surface of the substrate, so that the reduction in permeability can be more effectively suppressed, which is preferred.

[0328] The volume average particle size (D50) of the granular polymer in the coating liquid can be, for example, 1.0 μm or more and 12 μm or less. From the viewpoint of obtaining a suitable distribution state of the protruding granular polymer in the covering layer, the volume average particle size (D50) is preferably 1.5 μm or more, and preferably 10 μm or less, 6.0 μm or less, 5.0 μm or less, 3.5 μm or less, 3.0 μm or less, or 2.5 μm or less. If the volume average particle size (D50) is above the above lower limit, it is easy to prevent the aggregation of the granular polymers from each other. In addition, if the volume average particle size (D50) is below the above upper limit, the particle size difference with the inorganic filler can be controlled within a specified range, thereby easily and appropriately controlling the sedimentation of the granular polymer in the coating liquid. The volume average particle size of the granular polymer can be controlled, for example, by adjusting the polymerization time, polymerization temperature, raw material composition ratio, raw material input sequence and pH used to obtain the granular polymer.

[0329] The coating liquid may optionally contain additives. Examples of additives for the coating liquid include dispersants such as surfactants, thickeners, wetting agents, defoamers, and pH adjusters such as acids and alkalis.

[0330] Examples of methods for dispersing or dissolving the inorganic filler, particulate polymer and, if necessary, water-soluble polymer in the medium of the coating liquid include mechanical stirring using a ball mill, a bead mill, a planetary ball mill, a vibration ball mill, a sand mill, a colloid mill, an attritor, a roll mill, a high-speed impeller dispersion, a distributor, a homogenizer, a high-speed impact mill, an ultrasonic dispersion, and a stirring blade.

[0331] As a step for preparing the coating liquid, it is preferred that: first, a water-soluble polymer is added to the coating liquid in which the inorganic filler is dispersed, and then a resin binder and a granular polymer are added. By preparing the coating liquid in this order, the water-soluble polymer can adsorb and protect the metal ions contained in the inorganic filler, and the aggregation of the resin binder and the granular polymer can be prevented.

[0332] From the viewpoint of obtaining a suitable distribution state of the protruding granular polymer in the covering layer, the viscosity of the coating liquid is preferably greater than 10 mPa·s or greater than 20 mPa·s, and is preferably less than 100 mPa·s, less than 80 mPa·s, less than 60 mPa·s or less than 40 mPa·s.

[0333] In this embodiment, the thermoplastic polymer contained in the coating liquid is preferably a particle having a large particle size of 1 μm to 10 μm. Therefore, if the viscosity of the coating liquid is 10 mPa·s or more, the thermoplastic polymer can be prevented from settling in the coating liquid. On the other hand, if the viscosity of the coating liquid is 100 mPa·s or less, turbulence of the liquid is easily caused during stirring, and the dispersion of the granular polymer in the coating liquid flow becomes good, making it easier to control the coefficient of variation (CV) of the area (si) of the Voronoi polygon within the above range.

[0334] In addition, from the viewpoint of appropriately controlling the sedimentation of the granular polymer in the process of removing the solvent from the coating film to form a covering layer after coating, the viewpoint of improving the slope of the covering layer, and the viewpoint of improving the contact ratio between the granular polymer and the substrate surface, the viscosity of the coating liquid is preferably 10 mPa·s or more and 100 mPa·s or less. As means for controlling the viscosity of the coating liquid, there can be listed the adjustment of the aspect ratio of the inorganic filler, the coefficient of variation of the particle size distribution of the inorganic filler, and the type of thickener. By using these means, the viscosity of the coating liquid can be reduced during the fixation of the coating liquid (forming a covering layer by drying), and the curved liquid surface of the coating liquid to the granular polymer can be improved (improving wettability). As a result, the slope of the covering layer can be increased, and the adhesion to the electrode can be increased.

[0335] The substrate may be subjected to a surface treatment before coating. Surface treatment is preferred because it facilitates coating of the coating solution, improves adhesion between the substrate and the thermoplastic polymer, and makes it easy to control the 180° peel strength to be above 200 gf / cm.

[0336] Examples of the surface treatment method include corona discharge treatment, plasma treatment, mechanical roughening, solvent treatment, acid treatment, and ultraviolet oxidation. Examples of the surface treatment method include corona discharge treatment.

[0337] The method of applying the coating liquid to the substrate is not particularly limited as long as it is a method that can achieve a desired coating pattern, coating film thickness, and coating area.

[0338] Examples of coating methods include gravure coating, small-diameter gravure coating, reverse roll coating, transfer roll coating, kiss coating, dip coating, knife coating, air knife coating, blade coating, rod coating, extrusion coating, cast coating, die coating, screen printing, spray coating, and inkjet coating. Among these, gravure coating or spray coating is preferred because the degree of freedom of the coating shape of the particulate polymer is high and a preferred area ratio is easily obtained.

[0339] In the coating method, it is preferred to use a gravure coating method or the like at a high shear rate, and the shear rate is preferably 40,000 sec. -1 More than 120,000 seconds -1 When the shear rate is within this range, the dispersion of the particulate polymer as primary particles becomes favorable, and it becomes easier to control the 180° peel strength to 200 gf / cm or more.

[0340] The coating liquid may be stirred before or during coating so that the particulate polymer can be uniformly dispersed in the coating liquid for coating. Examples of stirring methods include:

[0341] A method of stirring the coating liquid in a supply tank using turbulence;

[0342] A method of subjecting the coating liquid to ultrasonic treatment (vibration / agitation treatment using ultrasonic waves) immediately before coating; etc.

[0343] From the viewpoint of obtaining a suitable distribution state of the protruding particulate polymer in the covering layer, it is advantageous to appropriately perform such stirring.

[0344] There are no particular limitations on the method of removing the medium from the coating film after coating, as long as it does not adversely affect the substrate and the coating layer. Examples include: a method of drying at a temperature below the melting point while fixing the substrate; a method of drying under reduced pressure at a low temperature; a method of immersing the polymer in a medium that is a poor solvent for the granular polymer and extracting the medium while solidifying the granular polymer into granules, etc.

[0345] From the viewpoint of adjusting the static friction coefficient of the coating layer to the above range and / or from the viewpoint of making a part of the surface of the protruding particulate polymer lack, it is preferable to control the conditions after the coating / drying step as follows:

[0346] The tension applied in the direction perpendicular to the surface of the coated surface in contact with the conveying roller is controlled to be above a predetermined value, for example, above 120 N / m;

[0347] Make the conveying roller speed that the coating surface contacts lower than the conveying speed of the separator;

[0348] The inorganic filler is formed into an inclined shape in such a way that the protruding particulate polymer does not slide off the surrounding inorganic filler portion;

[0349] The peel strength of the cover layer is increased, for example, to 200 gf / cm or more.

[0350] <Production of wound body of separator>

[0351] The obtained separator for an electrical storage device is preferably in the form of a wound body. By forming the separator into a wound body, it can be easily pulled out at high speed, and productivity can be improved in the production process of the electrical storage device.

[0352] 《Electrical Storage Equipment》

[0353] The power storage device of the present embodiment includes a separator for power storage device of the present embodiment. The power storage device is not particularly limited, and examples thereof include batteries such as non-aqueous electrolyte secondary batteries, capacitors, and capacitors. Among these, in order to utilize the advantages of the separator for power storage device of the present embodiment, a battery is preferred, a non-aqueous electrolyte secondary battery is more preferred, and a lithium ion secondary battery is further preferred.

[0354] The lithium ion secondary battery has a positive electrode, a negative electrode, a separator for the storage device of this embodiment disposed between the positive electrode and the negative electrode, and a non-aqueous electrolyte. The storage device of this embodiment has excellent characteristics such as storage performance by including the separator for the storage device, and in the case of the lithium ion secondary battery, the battery characteristics are excellent.

[0355] When the electrical storage device of the present embodiment is a lithium ion secondary battery, the positive electrode, the negative electrode, and the non-aqueous electrolyte are not limited, and known materials can be used for each.

[0356] As the positive electrode, a positive electrode having a positive electrode active material layer containing a positive electrode active material on a positive electrode current collector can be suitably used. As the positive electrode current collector, for example, aluminum foil can be cited. As the positive electrode active material, for example, lithium-containing composite oxides such as LiCoO2, LiNiO2, spinel-type LiMnO4 and olivine-type LiFePO4 can be cited. In addition to the positive electrode active material, the positive electrode active material layer can also appropriately contain a binder, a conductive material, etc.

[0357] As the negative electrode, a negative electrode having a negative electrode active material layer containing a negative electrode active material on a negative electrode current collector can be appropriately used. As the negative electrode current collector, for example, copper foil can be cited. As the negative electrode active material, for example, carbon materials such as graphite, non-graphitizable carbon, easily graphitizable carbon, and composite carbon can be cited; as well as silicon, tin, metallic lithium, and various alloy materials.

[0358] As the non-aqueous electrolyte, there is no particular limitation, and an electrolyte obtained by dissolving an electrolyte in an organic solvent can be used. As the organic solvent, for example, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate and ethyl methyl carbonate can be listed. As the electrolyte, for example, lithium salts such as LiClO4, LiBF4 and LiPF6 can be listed.

[0359] 《Manufacturing method of electric storage device》

[0360] The method for producing an electrical storage device using the separator of the present embodiment is not particularly limited, but the following method can be exemplified.

[0361] First, the separator of this embodiment is manufactured by the above method. The size and shape of the separator may be, for example, a longitudinal shape with a width of 10 mm to 500 mm, preferably 80 mm to 500 mm, and a length of 200 m to 10,000 m, preferably 1,000 m to 6,000 m.

[0362] Next, the positive electrode-separator-negative electrode-separator or negative electrode-separator-positive electrode-separator are stacked in the order of positive electrode-separator-negative electrode-separator, and wound into a circular or flat spiral shape to obtain a wound body. The wound body can be manufactured by storing it in a device can (such as a battery can) and then injecting an electrolyte. Alternatively, it can also be manufactured by folding the electrode and separator to form a wound body and placing it in a device container (such as an aluminum film) and injecting an electrolyte.

[0363] Specifically, a method in which a separator and an electrode including a current collector and an active material layer formed on at least one surface of the current collector are overlapped so that the covering layer faces the active material layer and then pressurized can be exemplified.

[0364] The pressing temperature is a temperature at which the adhesiveness can be effectively exhibited, preferably at T 1.00 It should be noted that T 1.00 It refers to the temperature at which the minimum value of DDSC is obtained from 0°C to 150°C when the value obtained by differentiating the heat flow difference per unit time measured by DSC (differential scanning calorimetry) with respect to temperature is defined as DDSC.

[0365] By T 1.00 The pressure is applied at a temperature above 35°C so that the covering layer is sufficiently deformed and good adhesion can be obtained. For example, it is preferably above 35°C. From the viewpoint of suppressing the clogging or thermal shrinkage of the holes in the separator caused by hot pressing, the pressure application temperature is preferably lower than the melting point of the material contained in the substrate, and more preferably below 130°C.

[0366] From the viewpoint of suppressing clogging of the pores in the separator, the pressing pressure is preferably 20 MPa or less. The pressing time may be 1 second or less when roller pressing is used, or several hours when surface pressing is used, but is preferably 2 hours or less from the viewpoint of productivity.

[0367] When the separator for a power storage device of the present embodiment is used and the above manufacturing process is performed, the press unwinding (press back) when the winding body including the electrode and the separator is press-formed can be suppressed. Therefore, the reduction of the yield rate in the device assembly process can be suppressed, and the production process time can be shortened.

[0368] Adhesion may also be imparted without pressurizing the wound body. Specifically, the following method may be exemplified: the wound body is stored in a device can and an electrolyte is injected, and adhesion is imparted between electrodes facing the covering layer of the separator by utilizing the pressure generated in the device can when manufacturing the electrical storage device or utilizing the pressure associated with expansion and contraction of the electrodes caused by charging and discharging of the electrical storage device.

[0369] The power storage device, particularly the lithium ion secondary battery manufactured as described above includes the separator of the present embodiment having high adhesion to the electrode and low thermal shrinkage, and therefore has excellent battery characteristics (rate characteristics) and excellent resistance to long-term continuous operation (cycle characteristics).

[0370] Example

[0371] Hereinafter, the embodiments of the present application will be described in detail by way of examples and comparative examples, but the present application is not limited to these examples and comparative examples.

[0372] 《Measurement and evaluation methods》

[0373] <Thickness of the inorganic filler portion of the covering layer, slope of the covering layer, and protrusion amount of the granular polymer>

[0374] The separator is frozen and cut, and its cross section is confirmed using SEM (model: S-4800, manufactured by HITACHI Corporation). Based on the obtained field of view, the thickness of the inorganic filler portion of the coating layer, the inclination of the coating layer, and the protrusion of the granular polymer are measured. Specifically, the separator sample is cut into pieces of about 1.5 mm × 2.0 mm and stained with ruthenium. The stained sample and ethanol are placed in a gelatin capsule, and after freezing it with liquid nitrogen, the sample is cut with a hammer. Osmium is evaporated on the cut sample and observed under the conditions of an acceleration voltage of 1.0 kV and 5000 times. As Figure 2 As schematically shown in FIG. 1 , in the SEM image of the cut sample cross section, the distance from the boundary line between the substrate and the covering layer to the outer surface of the covering layer was measured as the thickness L1 (μm) of the inorganic filler part of the covering layer.

[0375] In addition, the maximum distance L2 (μm) from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler formed into the inclined covering layer and the maximum distance L3 (μm) to the outline of the protruding granular polymer were measured, and the inclination L2 / L1 of the covering layer, the coverage of the protruding portion (L2-L1) / (L3-L1), and the protruding amount L3-L1 of the granular polymer were calculated. The inclination L2 / L1 of the covering layer, the coverage of the protruding portion (L2-L1) / (L3-L1), and the protruding amount L3-L1 of the granular polymer were measured at 200 locations, and the average value was calculated.

[0376] As a method for measuring L1, L2 and / or L3, a method of obtaining each value of L1 while polishing a cross section observed by SEM may be used.

[0377] 〈180° peel strength〉

[0378] The surface of the separator cut into 2mm×7mm on the opposite side of the covering layer to be measured was adhered to the glass plate with double-sided tape, and the tape (product name "Mending Tape MP-12", manufactured by 3M) was adhered to the covering layer. The front end of the tape was peeled off 5mm, and the front end of the tape was clamped with a clamp using a tensile tester (model: AG-IS, SLBL-1kN, manufactured by Shimadzu Corporation) so that the tape was peeled off at an angle of 180° relative to the surface direction of the separator. The tensile test was performed at a tensile speed of 50mm / sec, a temperature of 25 degrees, and a relative humidity of 40% to measure the tensile strength (N / m).

[0379] 〈Friction test〉

[0380] The surface of the separator sample on which the coating layer was formed was subjected to friction test with a table material SKD61 (surface roughness Ra: 0.4 μm) by the horizontal method twice along the TD using a MH-3 friction tester manufactured by Toyo Seiki Seisaku-sho Co., Ltd. under the conditions of a pulley mass of 200 g, a load capacity of 20 N, a contact area of ​​63 mm×63 mm (felt material), a test speed of 100 mm / min, a measurement distance of 30 mm, a temperature of 23°C, and a humidity of 50%, and the static friction coefficient was measured. The average values ​​thereof were calculated and shown in the following table. In the above friction test, the separator sample cut into 100 mm×100 mm, i.e., the test body, was set in such a manner that the back side of the test body was in contact with the surface of the felt material surface of the pulley.

[0381] 〈Contact ratio of protruding particulate polymer to substrate〉

[0382] The separator was frozen and cut, and its cross section was confirmed using SEM (model: S-4800, manufactured by HITACHI Corporation). Based on the obtained field of view, the thickness of the layer containing the thermoplastic polymer was measured. Specifically, the sample of the separator was cut into pieces of about 1.5 mm × 2.0 mm and stained with ruthenium. The stained sample and ethanol were placed in a gelatin capsule, and after freezing it with liquid nitrogen, the sample was cut with a hammer. Osmium was evaporated on the cut sample and observed under the conditions of an acceleration voltage of 1.0 kV and 5000 times. In the SEM image, for 200 granular polymers with cut surfaces protruding from the thickness of the inorganic filler part, the number of particles in contact with the substrate was measured as the contact ratio between the protruding granular polymer and the substrate.

[0383] <Ratio of the number of particulate polymers protruding from the thickness of the inorganic filler portion of the covering layer>

[0384] The separator was frozen and cut, and its cross section was confirmed using SEM (model: S-4800, manufactured by HITACHI Corporation). Based on the obtained visual field, the thickness of the layer containing the thermoplastic polymer was measured. Specifically, the sample of the separator was cut into pieces of about 1.5 mm × 2.0 mm and stained with ruthenium. The stained sample and ethanol were placed in a gelatin capsule, and after freezing it with liquid nitrogen, the sample was cut with a hammer. Osmium was evaporated on the cut sample and observed under the conditions of an acceleration voltage of 1.0 kV and 5000 times. In the SEM image, 200 granular polymers present on the cut surface were observed, and the number of granular polymers protruding from the thickness of the inorganic filler part of the covering layer was measured as the ratio of the number of granular polymers protruding from the thickness of the inorganic filler part of the covering layer.

[0385] 〈Dichloromethane soluble components〉

[0386] The following method is used to determine the dichloromethane soluble components in the substrate and separator. The substrate or separator sampled into 100×100 mm is de-electrified and weighed using a precision balance (W0(g)). Next, 200 ml of dichloromethane is added to a sealed container, and the above separator is immersed at room temperature for 15 minutes. Thereafter, the separator is taken out, dried at room temperature for 3 hours, de-electrified in the same manner as above, and weighed using a precision balance (W1(g)). The dichloromethane soluble components are calculated using the following formula.

[0387] Dichloromethane soluble content (%) = {(W1-W0) / W0}×100

[0388] 〈Total amount of metal cations〉

[0389] Take 0.60g of the separator into a pressurized decomposition container made of Teflon (registered trademark), add 10ml of sulfuric acid and seal it, and heat it in an air bath at 200°C for 15 hours. After cooling, the solution in the container is transferred to a 100ml volumetric flask made of resin and fixed to volume as a sample solution. The sample solution is measured by inductively coupled plasma atomic emission analysis (ICP-OES) (model "ICPE-9000", made by Shimadzu Corporation), and the content of each element is calculated using a standard curve made from a standard solution.

[0390] 〈Heat shrinkage ratio〉

[0391] As a sample, the separator is cut into 100 mm in MD and 100 mm in TD, and placed in an oven at 130°C or 150°C for 1 hour. At this time, the sample is sandwiched between two pieces of paper so that the warm air does not directly contact the sample. After the sample is taken out of the oven and cooled, the length (mm) is measured, and the heat shrinkage rate is calculated using the following formula. The measurement is performed in MD and TD, and the value of TD is expressed as the heat shrinkage rate.

[0392] Thermal shrinkage (%) = {(100-length after heating) / 100}×100

[0393] 〈Weight per unit area (g / m 2 )〉

[0394] The unit area weight is per unit area (1m 2 ) of the polyolefin microporous membrane. After sampling 1m×1m, the weight was measured using an electronic balance (AUW120D) manufactured by Shimadzu Corporation. It should be noted that when it is not possible to sample 1m×1m, an appropriate area was cut out and the weight was measured, and then converted to per unit area (1m 2 )’s weight (g).

[0395] 〈Thickness of substrate or separator〉

[0396] A 10 cm × 10 cm square sample was cut from the substrate or separator, and 9 locations (3 points × 3 points) were selected in a grid pattern. The thickness (μm) was measured at room temperature 23±2° C. using a micro thickness gauge (Toyo Seiki Seisaku-sho Co., Ltd., type: KBM). The average value of the measured values ​​at the 9 locations was calculated as the thickness of the substrate or separator.

[0397] 〈Porosity of substrate〉

[0398] Cut a 10 cm x 10 cm square sample from the substrate and calculate its volume (cm 3 ) and mass (g). Using these values, the density of the substrate was set to 0.95 (g / cm 3 ), and the porosity is calculated according to the following formula.

[0399] Porosity (%) = (1-mass / volume / 0.95) × 100

[0400] Density (g / cm 3 )〉

[0401] The density of the sample was measured by a density gradient tube method (23° C.) in accordance with JIS K7112:1999.

[0402] 〈Breathability〉

[0403] For the substrate and the separator for a power storage device, the air permeability was measured according to JIS P-8117 using a Gurley air permeometer G-B2 (model name) manufactured by Toyo Seiki Co., Ltd. When the covering layer exists only on one side of the substrate, a needle may be inserted from the side where the covering layer exists.

[0404] <Puncture Strength>

[0405] The substrate was fixed using a hand-held compression tester KES-G5 (model name) manufactured by KATOTECH with a sample holder having an opening diameter of 11.3 mm. Next, a puncture test was performed at a puncture speed of 2 mm / s at 25°C using a needle having a curvature radius of 0.5 mm at the front end of the fixed substrate, and the maximum puncture load was measured as the puncture strength (gf). In the case where the covering layer exists only on one side of the substrate, the needle can be inserted from the side where the covering layer exists.

[0406] 〈Average pore size of polyolefin microporous membrane〉

[0407] It is known that the fluid inside the capillary follows Knudsen flow when the mean free path of the fluid is greater than the pore size of the capillary, and follows Poiseuille flow when the mean free path of the fluid is less than the pore size of the capillary. Therefore, it is assumed that the flow of air in the air permeability measurement of the layer containing the thermoplastic polymer follows Knudsen flow, and the flow of water in the water permeability measurement of the substrate follows Poiseuille flow.

[0408] The average pore size d (μm) of the polyolefin microporous membrane is calculated based on the air permeation rate constant R gas (m 3 / (m 2 ·sec·Pa)), water permeation rate constant R liq (m 3 / (m 2 ·sec·Pa)), air molecular velocity ν (m / sec), water viscosity η (Pa·sec), standard pressure Ps (=101325Pa), porosity ε (%), and film thickness L (μm) can be calculated using the following formula.

[0409] d=2ν×(R liq / R gas )×(16η / 3Ps)×10 6

[0410] Here, R gas The air permeability (sec) was calculated using the following formula.

[0411] R gas =0.0001 / (air permeability×(6.424×10 -4 )×(0.01276×101325))

[0412] In addition, R liq According to the water permeability (cm 3 / (cm 2 ·sec·Pa)) can be calculated using the following formula.

[0413] R liq = Water permeability / 100

[0414] It should be noted that the water permeability was determined as follows. A layer containing a thermoplastic polymer pre-immersed in ethanol was placed in a stainless steel permeable dish having a diameter of 41 mm. After the ethanol in the layer was washed with water, water was allowed to pass through at a pressure difference of about 50,000 Pa. The water permeability (cm) after 120 seconds was calculated. 3 ), calculate the water permeability per unit time, unit pressure and unit area, and use it as the water permeability.

[0415] In addition, ν is calculated based on the gas constant R (=8.314), absolute temperature T (K), pi, and the average molecular weight of air M (=2.896×10 -2 kg / mol), and use the following formula to calculate.

[0416] ν=((8R×T) / (π×M)) 1 / 2

[0417] 〈Glass transition temperature of thermoplastic polymers〉

[0418] An appropriate amount of an aqueous dispersion containing a thermoplastic polymer (solid content = 38 parts by mass or more and 42 parts by mass or less, pH = 9.0) was weighed into an aluminum dish and allowed to stand at room temperature for 24 hours to obtain a dry film. About 17 mg of the dry film was filled into an aluminum container for measurement, and a DSC curve and a DDSC curve under a nitrogen atmosphere were obtained using a DSC measuring device (manufactured by Shimadzu Corporation, model name "DSC6220"). The measurement conditions are as follows.

[0419] The first stage of heating program: start at 30℃, increase the temperature at a rate of 10℃ per minute, and maintain it for 5 minutes after reaching 150℃.

[0420] The second stage of cooling program: start cooling from 110℃ at a rate of 10℃ per minute. After reaching -50℃, maintain for 5 minutes.

[0421] The third stage of temperature increase program: the temperature was increased from -50°C to 150°C at a rate of 10°C per minute. During the third stage of temperature increase, DSC and DDSC data were acquired.

[0422] The glass transition temperature was determined by the method described in JIS-K7121 for the obtained DSC curve. Specifically, the temperature at the intersection of the following straight line and the curve was taken as the glass transition temperature (Tg), wherein the straight line was a straight line obtained by extending the low temperature side baseline in the DSC curve to the high temperature side and the straight line obtained by extending the high temperature side baseline in the DSC curve to the low temperature side in the longitudinal direction, and the curve was a curve of the step-like change portion of the glass transition.

[0423] 〈Aspect Ratio of Inorganic Filler in Covering Layer〉

[0424] The surface of the separator for storage device deposited with osmium was observed using a scanning electron microscope (SEM) (model "S-4800", manufactured by HITACHI) at an accelerating voltage of 1.0 kV and 10,000 times, and the aspect ratio was thus determined. In the SEM image, the aspect ratio was obtained by image processing of the inorganic filler in the covering layer. In the case where the inorganic fillers are bonded to each other, an inorganic filler whose longitudinal and lateral lengths can be clearly identified as an inorganic filler monomer is selected, and the aspect ratio is calculated based on them.

[0425] Specifically, 10 inorganic fillers whose lengths in the longitudinal and lateral directions can be clearly identified are selected, and the average value of the value obtained by dividing the length of the major axis of each inorganic filler by the length of the minor axis is taken as the aspect ratio. When there are less than 10 inorganic fillers whose lengths in the longitudinal and lateral directions can be clearly identified in one field of view, 10 are selected from images of multiple fields of view.

[0426] 〈Particle size distribution and average particle size of inorganic fillers〉

[0427] The particle size distribution of the inorganic filler was measured using a particle size measuring device (manufactured by Nikkiso Co., Ltd., product name "Microtrac UPA150"). The sample solution measured used a dispersion before coating, and as the measurement conditions, load index = 0.20, measurement time = 300 seconds, the value of the standard deviation SD of the volume average particle size (D50) in the obtained data was divided by the value of D50, thereby calculating the particle size distribution (Cv value) of the inorganic filler.

[0428] <Volume average particle size (D50) of the thermoplastic polymer and the volume average particle size (D50) of the resin binder in the aqueous dispersion>

[0429] The volume average particle size (D50) of the thermoplastic polymer in the aqueous dispersion and the volume average particle size (D50) of the resin binder were measured using a particle size measuring device (manufactured by Nikkiso Co., Ltd., product name "Microtrac UPA150"). As the measurement conditions, the load index = 0.20 and the measurement time are set to 300 seconds, and the value of the particle size (D50) at which the cumulative volume becomes 50% in the obtained data is recorded as the volume average particle size (D50).

[0430] 〈Observation of the presence or absence of defects on the spherical surface of granular polymer and calculation of the defect rate〉

[0431] The cross section of the separator for a storage device on which osmium was deposited was observed using a scanning electron microscope (SEM) (model "S-4800", manufactured by HITACHI Corporation) at an accelerating voltage of 1.0 kV and a magnification of 10,000 times to measure the cross section. Specifically, for 200 arbitrary particulate polymers, Figure 8As shown in the example, the maximum width (W) in the horizontal direction relative to the separator surface and the maximum height (H) in the vertical direction relative to the separator surface are measured, and the maximum height (H) is divided by the maximum width (W) to calculate the defect rate, and their average value is taken as the defect rate of the granular polymer.

[0432] <Volume average particle size (D50) and particle size distribution of particulate polymer in the covering layer>

[0433] The cross section of the separator for a storage device deposited with osmium was observed using a scanning electron microscope (SEM) (model "S-4800", manufactured by HITACHI Corporation) at an accelerating voltage of 1.0 kV and a magnification of 10,000 times to measure. Specifically, 200 circle-equivalent diameters of an arbitrary particulate polymer were measured, and the number average particle diameter MN and the volume average particle diameter MV were calculated from these values, and the particle size distribution of the particulate polymer was calculated as MV / MN.

[0434] 〈Surface observation and Voronoi segmentation of the covering layer〉

[0435] The surface of the separator for storage device deposited with osmium was subjected to elemental mapping using a scanning electron microscope (SEM) (model "SU-8220", manufactured by HITACHI) and energy dispersive X-ray spectroscopy (EDX) (model "ULTIM EXTREME", manufactured by Oxford). At this time, the SEM detector selected secondary electrons, set the acceleration voltage to 3 kV, and the mapping accumulation number to 20 times. Depending on the particle size of the granular polymer, the magnification was 500 times or 3000 times. Figure 7 As shown, the mapping measurement of carbon atoms on the surface of the cover layer on the separator was carried out in 10 fields of view.

[0436] For the protruding granular polymers contained in these 10 fields of view, the area of ​​the Voronoi polygon (s i ), the total number (n), mean (m), standard deviation (sd), and coefficient of variation (cv) of Voronoi polygons.

[0437] Specifically, based on the mapping image of carbon atoms, Gausian Blur processing (Sigma=5) was performed using image processing software (ImageJ), and then binarization was performed using the Threshold function (Auto), and then Watershed processing was performed.

[0438] The processed image is subjected to Voronoi segmentation using cv2.Subdiv2D.getVoronoiFacetList Method of opencv-python library (version 4.5.4.60) of the programming language Python.

[0439] In addition, when Voronoi segmentation is performed in the observation field, the unclosed area is not used as a target for calculating the area of ​​the Voronoi polygon.

[0440] 〈Ratio of falling off of granular polymer〉

[0441] For the surface of the separator for storage devices deposited with osmium, a scanning electron microscope (SEM) (model "SU-8220", manufactured by HITACHI) and an energy dispersive X-ray spectrometer (EDX) (model "ULTIM EXTREME", manufactured by Oxford) were used to perform element mapping. At this time, the SEM detector selected secondary electrons, set the acceleration voltage to 3 kV, and the mapping accumulation number to 20 times. According to the particle size of the granular polymer, the mapping measurement of carbon atoms at a magnification of 500 to 3000 times was implemented in 10 fields of view. According to the mapping image of the carbon atoms, after Gausian Blur processing (Sigma = 5) was performed using image processing software (ImageJ), the Threshold function (Auto) was used for binarization, and the projection area of ​​the granular polymer when looking down on the surface of the covering layer was calculated. The average value of these 10 fields of view was taken as the projection area (Sr) of the granular polymer when looking down on the surface of the covering layer. In addition, the SEM images of the 10 fields of view in which the above-mentioned carbon atom mapping measurement was performed were similarly processed using image processing software (ImageJ), thereby calculating the sliding area of ​​the granular polymer when looking down on the surface of the covering layer. The average value of these 10 fields of view was taken as the shedding area (Sd) of the granular polymer when looking down on the surface of the covering layer. Based on the calculated values ​​of Sr and Sd, the shedding area ratio of the granular polymer Sd / (Sr+Sd)×100(%) was calculated.

[0442] 〈Rate Characteristics〉

[0443] a. Preparation of positive electrode

[0444] The positive electrode active material is a nickel, manganese, cobalt composite oxide (NMC) (Ni:Mn:Co = 1:1:1 (element ratio), density 4.70 g / cm 3 ) 90.4 parts by mass, graphite powder (KS6) as a conductive additive (density 2.26 g / cm 3 , number average particle size 6.5 μm) 1.6 parts by mass and acetylene black powder (AB) (density 1.95 g / cm 3, number average particle size 48nm) 3.8 parts by mass, and polyvinylidene fluoride (PVdF) (density 1.75g / cm 3 ) were mixed at a ratio of 4.2 parts by mass and dispersed in N-methylpyrrolidone (NMP) to prepare a slurry.

[0445] The slurry was applied to one side of a 20 μm thick aluminum foil, which was to be the positive electrode current collector, using a die coater, and dried at 130°C for 3 minutes, followed by compression molding using a roll press to produce a positive electrode. The amount of positive electrode active material applied at this time was 109 g / m 2 .

[0446] b. Preparation of negative electrode

[0447] Graphite powder A (density 2.23 g / cm 3 , number average particle size 12.7 μm) 87.6 parts by mass and graphite powder B (density 2.27 g / cm 3 , number average particle size 6.5 μm), 9.7 parts by mass of ammonium salt of carboxymethyl cellulose as a binder (converted on a solid basis) (an aqueous solution with a solid content concentration of 1.83 parts by mass), and 1.7 parts by mass of diene rubber latex (converted on a solid basis) (an aqueous solution with a solid content concentration of 40 parts by mass) are dispersed in purified water to prepare a slurry.

[0448] The slurry was applied to one side of a 12 μm thick copper foil, which was to be the negative electrode current collector, using a die coater, and dried at 120°C for 3 minutes, followed by compression molding using a roll press to produce a negative electrode. The amount of negative electrode active material applied was 5.2 g / m 2 .

[0449] c. Preparation of non-aqueous electrolyte

[0450] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) so as to have a concentration of 1.0 mol / L.

[0451] d.Battery assembly

[0452] Cut the separator or substrate into The positive and negative electrodes are cut into The negative electrode, separator or substrate, and positive electrode are stacked in order so that the active material surfaces of the positive electrode and the negative electrode face each other, and are stored in a stainless steel metal container with a lid. The container and the lid are insulated, the container is in contact with the copper foil of the negative electrode, and the lid is in contact with the aluminum foil of the positive electrode. 0.4 ml of the aforementioned non-aqueous electrolyte is injected into the container and sealed, thereby assembling a battery.

[0453] e. Evaluation of rate characteristics

[0454] The simple battery assembled in d. is charged at 25°C at a current value of 3mA (about 0.5C) to a battery voltage of 4.2V, then maintained at 4.2V, and the current value is reduced from 3mA. The initial charging after the battery is made is performed for a total of about 6 hours by the above method. Thereafter, it is discharged at a current value of 3mA to a battery voltage of 3.0V. Next, at 25°C, it is charged at a current value of 6mA (about 1.0C) to a battery voltage of 4.2V, then maintained at 4.2V, and the current value is reduced from 6mA. The charging is performed for a total of about 3 hours by the above method. Thereafter, the discharge capacity when the battery voltage is discharged at a current value of 6mA to 3.0V is taken as the 1C discharge capacity (mAh).

[0455] Next, at 25°C, charge the battery to a voltage of 4.2V at a current value of 6mA (about 1.0C), keep it at 4.2V, and reduce the current value from 6mA. By the above method, charge for a total of about 3 hours. Thereafter, discharge the battery to a voltage of 3.0V at a current value of 12mA (about 2.0C) as the 2C discharge capacity (mAh). Next, calculate the ratio of the 2C discharge capacity to the 1C discharge capacity, and use its value as the rate characteristic.

[0456] Rate characteristics (%) = (2C discharge capacity / 1C discharge capacity) × 100

[0457] Evaluation criteria of rate characteristics (%)

[0458] A (good): rate characteristics exceeding 85%

[0459] B (pass): rate characteristic is more than 80% and less than 85%

[0460] C (poor): rate characteristics are 80% or less

[0461] <Adhesion strength to the electrode (before electrolyte injection)>

[0462] The separator was cut into a rectangular shape of 20 mm wide x 70 mm long and superposed on the positive electrode cut into a size of 15 mm x 60 mm to prepare a laminate of the separator and the electrode. The laminate was pressurized under the following conditions.

[0463] Temperature: 90℃

[0464] Pressurization pressure: 1MPa

[0465] Pressurization time: 5 seconds

[0466] The peel strength between the separator and the electrode after pressurization was measured by performing a 90° peel test at a peeling speed of 50 mm / min using a dynamometer ZP5N and MX2-500N (product name) manufactured by IMADA. At this time, the average value of the peel strength in the peel test of 40 mm in length performed under the above conditions was used as the peel strength.

[0467] Adhesion evaluation criteria

[0468] A (excellent): peel strength is 5N / m or more

[0469] B (good): Peel strength is 2 N / m or more and less than 5 N / m

[0470] C (pass): peel strength is 1 N / m or more and less than 2 N / m

[0471] D (unqualified): peel strength is less than 1N / m

[0472] <Adhesion to the electrode (after electrolyte injection)>

[0473] The separator was cut into a rectangular shape of 20 mm wide × 70 mm long, and overlapped with the positive electrode cut into a size of 15 mm × 60 mm to make a laminate of the separator and the electrode. The laminate was inserted into an aluminum laminate film and 0.4 ml of an electrolyte (containing 1 mol / L of LiPF6 and a mixture of EC / DEC = 1 / 2) was added. After sealing, it was left to stand for 12 hours and pressurized under the following conditions.

[0474] Temperature: 90℃

[0475] Pressurization pressure: 1MPa

[0476] Pressurization time: 1 minute

[0477] The peel strength between the separator and the electrode after pressurization was measured by performing a 90° peel test at a peeling speed of 50 mm / min using a dynamometer ZP5N and MX2-500N (product name) manufactured by IMADA. At this time, the average value of the peel strength in the peel test of 40 mm in length performed under the above conditions was used as the peel strength.

[0478] Adhesion evaluation criteria

[0479] A (good): peel strength is 5 N / m or more

[0480] B (pass): peel strength is 2 N / m or more and less than 5 N / m

[0481] C (poor): peel strength is 1 N / m or more and less than 2 N / m

[0482] D (unqualified): peel strength is less than 1N / m

[0483] 〈Powder shedding〉

[0484] A tape (manufactured by 3M) with a width of 12 mm and a length of 100 mm was pasted on the cover surface of the separator. The force when the tape was peeled off from the sample at a speed of 50 mm / min was measured using a 90° peel strength tester (manufactured by IMADA, product name IP-5N). Based on the obtained measurement results, the adhesive strength was evaluated according to the following evaluation criteria.

[0485] A (good): 59N / m (6gf / mm) or more

[0486] B (allowable): 40 N / m or more and less than 59 N / m

[0487] C (bad): less than 40N / m

[0488] 〈Cycling Characteristics〉

[0489] a. Preparation of positive electrode

[0490] The positive electrode active material is a nickel, cobalt, aluminum composite oxide (NCA) (Ni:Co:Al = 90:5:5 (element ratio), density 3.50 g / cm 3 ) 100 parts by mass, acetylene black powder (AB) as a conductive material 1.25 parts by mass, and polyvinylidene fluoride (PVdF) as a binder 1.0 parts by mass are mixed and dispersed in N-methylpyrrolidone (NMP) to prepare a slurry. The slurry is applied to both sides of an aluminum foil with a thickness of 15 μm, which serves as a positive electrode collector, using a die coater, and after drying at 130°C for 3 minutes, a roll press is used to perform compression molding to produce a positive electrode. The amount of positive electrode active material applied at this time is 456 g / m 2 .

[0491] b. Preparation of negative electrode

[0492] 86.0 parts by mass of graphite powder and 4.5 parts by mass of silicon oxide (SiO) as negative electrode active materials, as well as 1 part by mass of sodium salt of carboxymethyl cellulose and 1.0 part by mass of styrene-butadiene rubber (SBR) as binders were dispersed in purified water to prepare slurry. The slurry was applied to both sides of a 7.5 μm thick copper foil, which served as a negative electrode collector, using a die coater. After drying at 120°C for 3 minutes, compression molding was performed using a roller press to produce a negative electrode. The amount of negative electrode active material applied at this time was 266 g / m 2 .

[0493] c. Preparation of non-aqueous electrolyte

[0494] A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:dimethyl carbonate:ethyl methyl carbonate=25:70:5 (weight ratio) to a concentration of 1.4 mol / L.

[0495] d.Battery assembly

[0496] The positive electrode (width 63 mm), the negative electrode (width 64 mm), and the separator (width 67 mm) were stacked and wound into a spiral shape to produce a wound body. The wound body was placed in a cylindrical battery can with an outer diameter of 21 mm and a height of 70 mm, and the non-aqueous electrolyte was injected and sealed to assemble the battery.

[0497] e. Evaluation of cycle characteristics

[0498] The battery assembled in d. is charged at 25°C at a current value of 3mA (about 0.5C) until the battery voltage reaches 4.2V, and then it is maintained at 4.2V and charged until the current value reaches 50mA. Thereafter, it is discharged at 0.2C until the battery voltage reaches 2.5V, and the initial capacity is calculated. Next, after charging at 0.3C until the battery voltage reaches 4.2V, it is maintained at 4.2V and charged until the current value reaches 50mA, and then it is discharged at 1C until the battery voltage reaches 2.5V. This is regarded as one cycle, and the charge and discharge are repeated. In addition, the capacity retention rate after 500 cycles relative to the initial capacity (capacity of the first cycle) is used to evaluate the cycle characteristics according to the following benchmarks.

[0499] A (good): 80% or more capacity retention rate

[0500] B (qualified): 75% or more and less than 80% capacity maintenance rate

[0501] C (failure): less than 75% capacity maintenance rate

[0502] 《Example of manufacturing base material》

[0503] <Manufacturing of polyolefin microporous membrane B1>

[0504] Using a drum blender, 45 parts by mass of a homopolymer high-density polyethylene with an Mv of 700,000, 45 parts by mass of a homopolymer high-density polyethylene with an Mv of 300,000, and 10 parts by mass of a mixture of a homopolymer polypropylene with an Mv of 400,000 and a homopolymer polypropylene with an Mv of 150,000 (mass ratio = 4:3) were dry blended. 1 part by mass of tetrakis-[methylene-(3',5'-di-tert-butyl-4'-hydroxyphenyl) propionate]methane as an antioxidant was added to 99 parts by mass of the obtained polyolefin mixture, and dry blending was performed again using a drum blender to obtain a mixture. The obtained mixture was supplied to a twin-screw extruder under a nitrogen atmosphere using a feeder.

[0505] In addition, liquid paraffin (kinematic viscosity 7.59×10 -5 m 2 The feeder and pump operating conditions were adjusted so that the proportion of the liquid paraffin in 100 parts by mass of the total extruded mixture was 65 parts by mass, that is, the proportion of the resin composition was 35 parts by mass.

[0506] Next, they were melt-kneaded while being heated to 230°C in a twin-screw extruder, and the resulting molten kneaded product was extruded through a T-die onto a cooling roll whose surface temperature was controlled to be 80°C. The extrudate was brought into contact with the cooling roll, cast, and cooled to solidify, thereby obtaining a sheet-like formed product with a thickness of 1.5 mm.

[0507] The sheet was stretched by a simultaneous biaxial stretching machine at a ratio of 7×6.4 times and a temperature of 20° C., immersed in dichloromethane, and dried after extraction to remove liquid paraffin, and stretched 1.8 times in the transverse direction at a temperature of 130° C. by a tenter stretching machine. Thereafter, the stretched sheet was relaxed by about 10% in the width direction and heat-treated to obtain a polyolefin microporous membrane B1 as a substrate.

[0508] The obtained polyolefin microporous membrane was evaluated according to the above method. The evaluation results are shown in the following table.

[0509] <Manufacturing of Polyolefin Microporous Membrane B2>

[0510] The polyolefin microporous membrane B2 was produced in the same manner as the polyolefin microporous membrane B1 except that the thickness of the sheet-like molded product was changed to 0.5 mm. Table 1 shows the results of the measurements and evaluations similarly performed on the polyolefin microporous membrane B2.

[0511] [Table 1]

[0512] Table 1. Substrate

[0513] Polyolefin microporous membrane No. B1 B2 <![CDATA[Grammage (g / m 2 )]]> 6.4 3.5 Thickness(μm) 12 6 Porosity (%) 44 37 <![CDATA[Air permeability (seconds / 100 cm 3 )]]> 150 140 Puncture strength (gf) 500 255 Average pore size (nm) 50 50 Dichloromethane soluble content (mass %) 0.7 0.5

[0514] 《Example of Preparation of Aqueous Dispersion of Granular Polymer》

[0515] <Preparation of Aqueous Dispersion A1 of Particulate Polymer>

[0516] Into a reaction container equipped with a stirrer, a reflux condenser, a dropping tank and a thermometer, 70.4 parts by mass of ion exchange water, 0.5 parts by mass of "Aqualon KH1025" (a registered trademark, a 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd., referred to as "KH1025" in the table. The same shall apply hereinafter), and 0.5 parts by mass of "ADEKA REASOAP SR1025" (a registered trademark, a 25% aqueous solution manufactured by ADEKA Corporation, referred to as "SR1025" in the table. The same shall apply hereinafter) were added, and the internal temperature of the reaction container was raised to 95°C. Thereafter, while maintaining the internal temperature of the container at 95°C, 7.5 parts by mass of ammonium persulfate (2% aqueous solution) (referred to as "APS(aq)" in the table. The same shall apply hereinafter) were added.

[0517] On the other hand, a mixture of 71.5 parts by mass of methyl methacrylate (MMA), 18.9 parts by mass of n-butyl acrylate (BA), 2 parts by mass of 2-ethylhexyl acrylate (EHA), 0.1 parts by mass of methacrylic acid (MAA), 0.1 parts by mass of acrylic acid (AA), 2 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of acrylamide (AM), 0.4 parts by mass of glycidyl methacrylate (GMA), 0.4 parts by mass of trimethylolpropane triacrylate (A-TMPT) (manufactured by Shin-Nakamura Chemical Industry Co., Ltd.), 0.3 parts by mass of γ-methacryloxypropyltrimethoxysilane (AcSi), 3.0 parts by mass of KH1025, 3.0 parts by mass of SR1025, 0.05 parts by mass of sodium p-styrenesulfonate (NaSS), 7.5 parts by mass of ammonium persulfate (2% aqueous solution), and 52 parts by mass of ion-exchanged water was mixed with a homogenizer for 5 minutes to prepare an emulsion. The obtained emulsion was added dropwise from the dropping tank to the above reaction vessel. The addition was started 5 minutes after the addition of the aqueous ammonium persulfate solution to the reaction vessel, and the entire amount of the emulsion was added dropwise over 150 minutes. During the addition of the emulsion, the internal temperature of the container was maintained at 80°C. At this time, the stirring bar previously placed in the reaction vessel was stirred by a magnetic stirrer.

[0518] After the addition of the emulsion was completed, the temperature inside the reaction container was maintained at 80°C for 90 minutes, and then cooled to room temperature to obtain an emulsion. The obtained emulsion was adjusted to pH = 9.0 using an aqueous ammonium hydroxide solution (25% aqueous solution) to obtain an acrylic copolymer latex (aqueous dispersion A1) having a concentration of 40 parts by mass. The glass transition temperature (Tg) and volume average particle size (D50) of the thermoplastic polymer contained in the obtained aqueous dispersion A1 were evaluated using the above method. The results are shown in the table below.

[0519] <Preparation of aqueous dispersions A2 to A5 of granular polymer>

[0520] Aqueous dispersions A2 to 5 were obtained in the same manner as aqueous dispersion A1 except that the composition of the emulsion was changed as shown in the following table, and the physical properties were evaluated. The obtained results are shown in the following table.

[0521] <Preparation of aqueous dispersion A1-1 of granular polymer>

[0522] A portion of the aqueous dispersion A1 was taken and multi-stage polymerization was performed using it as a seed polymer to synthesize the aqueous dispersion A1-1. Specifically, first, a mixture of 20 parts by mass of the aqueous dispersion A1 and 70.4 parts by mass of ion exchange water was added to a reaction vessel equipped with a stirrer, a reflux condenser, a dropping tank and a thermometer, and the internal temperature of the reaction vessel was raised to 80°C. Thereafter, 7.5 parts by mass of ammonium persulfate (2% aqueous solution) was added while maintaining the internal temperature of the container at 80°C. The above is the initial charge.

[0523] On the other hand, a mixture of 71.5 parts by mass of methyl methacrylate (MMA), 18.9 parts by mass of n-butyl acrylate (BA), 2 parts by mass of 2-ethylhexyl acrylate (EHA), 0.1 parts by mass of methacrylic acid (MAA), 0.1 parts by mass of acrylic acid (AA), 2 parts by mass of 2-hydroxyethyl methacrylate (HEMA), 5 parts by mass of acrylamide (AM), 0.4 parts by mass of glycidyl methacrylate (GMA), 0.4 parts by mass of trimethylolpropane triacrylate (A-TMPT), 0.3 parts by mass of γ-methacryloxypropyltrimethoxysilane (AcSi), 3 parts by mass of KH1025, 3 parts by mass of SR1025, 0.05 parts by mass of sodium p-styrenesulfonate (NaSS), 7.5 parts by mass of ammonium persulfate (2% aqueous solution), and 52 parts by mass of ion-exchanged water was mixed with a homogenizer for 5 minutes to prepare an emulsion. The obtained emulsion was dropped from a dropping tank into the above reaction container. The ammonium persulfate aqueous solution was added to the reaction container and the dropwise addition was started 5 minutes later. The entire amount of the emulsion was added dropwise over 150 minutes. During the dropwise addition of the emulsion, the internal temperature of the container was maintained at 80° C. At this time, the stirring bar previously placed in the reaction container was stirred using a magnetic stirrer.

[0524] After the dropwise addition of the emulsion was completed, the reaction vessel was stirred for 90 minutes while maintaining the internal temperature at 80°C, and then cooled to room temperature to obtain an emulsion. The obtained emulsion was adjusted to pH = 9.0 using an aqueous ammonium hydroxide solution (25% aqueous solution) to obtain an acrylic copolymer latex (aqueous dispersion A1-1) having a concentration of 40 parts by mass. The obtained aqueous dispersion A1-1 was evaluated using the above method. The results obtained are shown in Table 2.

[0525] <Preparation of Aqueous Dispersions A2-1, A3-1 to A3-8, A4-1, and A5-1>

[0526] The composition of the seed polymer, monomer, and other raw materials was changed as described in Table 2. In addition, copolymer latex (water dispersions A2-1, A3-1 to A3-8, A4-1, and A5-1) was obtained in the same manner as water dispersion A1-1. The obtained water dispersions were evaluated using the above-mentioned methods. The obtained results are shown in Table 2.

[0527] [Table 2-1]

[0528]

[0529] [Table 2-2]

[0530]

[0531] <Abbreviation>

[0532] Emulsifier

[0533] KH1025: "Aqualon KH1025" registered trademark, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., 25% aqueous solution

[0534] SR1025: "ADEKAREASOAP SR1025" registered trademark, manufactured by ADEKA Co., Ltd., 25% aqueous solution

[0535] NaSS: Sodium p-styrene sulfonate

[0536] Initiator

[0537] APS(aq): ammonium persulfate (2% aqueous solution)

[0538] ·monomer

[0539] MAA: Methacrylic acid

[0540] AA: Acrylic acid

[0541] MMA: Methyl Methacrylate

[0542] BA: n-butyl acrylate

[0543] BMA: n-butyl methacrylate

[0544] EHA: 2-Ethylhexyl Acrylate

[0545] CHMA: Cyclohexyl methacrylate

[0546] St:Styrene

[0547] AN: Acrylonitrile

[0548] HEMA: 2-Hydroxyethyl Methacrylate

[0549] AM: Acrylamide

[0550] GMA: Glycidyl Methacrylate

[0551] A-TMPT: Trimethylolpropane triacrylate

[0552] AcSi: γ-methacryloxypropyltrimethoxysilane

[0553] 《Example of manufacturing separator》

[0554] <Example 1>

[0555] 0.3 parts by mass of an aqueous solution of ammonium polycarboxylate (SN Dispersant 5468 manufactured by SANNOPCO) and 100 parts by mass of aluminum hydroxide (boehmite, average particle size 450 nm) as an inorganic filler were mixed with 100 parts by mass of water, and the mixture was treated with a bead mill to obtain a pre-coating dispersion. In the pre-coating dispersion, 0.2 parts by mass of carboxymethyl cellulose (CMC) as a water-soluble polymer component was mixed with 100 parts by mass of the inorganic filler, and then 4 parts by mass of an acrylic latex suspension (solid content concentration 40%, volume average particle size 150 nm, Tg-10°C) as a resin binder and 10 parts by mass of the aqueous dispersion A3-5 were further mixed and uniformly dispersed to prepare a coating liquid (solid content 40 parts by mass) containing a thermoplastic polymer.

[0556] The two sides of the polyolefin microporous membrane B1 were surface treated by corona discharge treatment. Thereafter, the coating solution was applied to one side of the polyolefin microporous membrane B1 using a gravure coater. It should be noted that the coating solution was stirred using a Bernoulli flow stirring body BEAG (manufactured by Medec, with a rotation speed of 650 rpm) in the coating solution supply tank, and the shear rate based on the gravure coater was 80,000 sec. -1 The coverage ratio of the covering layer to the polyolefin microporous membrane at this time was 100%. Thereafter, the applied coating liquid was dried at 60° C. to remove water. In this manner, a separator having a covering layer formed on one surface of the polyolefin microporous membrane B1 was obtained.

[0557] <Examples 2 to 15 and Comparative Examples 1 to 4>

[0558] Separators of Examples and Comparative Examples were obtained in the same manner as in Example 1 except that the polyolefin microporous membrane, the composition of the coating liquid, the coating conditions, etc. were changed as described in the following table.

[0559] In Comparative Example 1, a tilted paddle stirring body was used to stir the coating liquid.

[0560] In the separators of Examples 2 to 15 and Comparative Examples 1 and 2, the particulate polymer was dispersed in the form of primary particles, and in the separator of Comparative Example 4, the particulate polymer was dispersed in the form of secondary particles.

[0561] <Evaluation of the presence or absence of curling, and evaluation of winding deviation and step deviation>

[0562] (Curl value)

[0563] The separator was cut into MD 20 cm x TD 5 cm and placed on a flat table. After 30 seconds, the MD length (A cm) of the microporous membrane in contact with the table was measured, and the curl value was obtained by the following formula.

[0564] [Curl value] = 20cm-Acm

[0565] As the MD length (Acm) of the separator in contact with the stage, all the parts of the microporous membrane in contact with the stage in the TD direction were measured. The measurement was performed under the conditions of a temperature of 23±2° C. and a relative humidity of 40%. The evaluation criteria of the curl value are shown below.

[0566] (Winding offset)

[0567] As an index of winding stability, winding deviation after division was evaluated.

[0568] Using a splitter TH4C (trade name) manufactured by Nishimura Manufacturing Co., Ltd., the separator was split into 60 mm wide under the conditions of a withdrawal tension of 100 N / m, a winding tension of 100 N / m, and a travel speed of 100 m / min, and then 2000 m was wound on a 3-inch paper tube to obtain a wound body. The degree of winding deviation of the wound body at this time was evaluated. It should be noted that the case where a deviation of less than 0.3 mm was generated in the split state was judged as no winding deviation, and the case where a deviation of more than 0.3 mm was generated was judged as having a winding deviation.

[0569] The evaluation was performed on 10 rolls of the wound body, and the winding deviation was evaluated based on the number of rolls judged to have winding deviation. The evaluation criteria of the winding deviation are as follows.

[0570] (Step offset)

[0571] As an index of the impact resistance stability of a separator roll having a roll length of 2000 m wound around a 3-inch paper tube obtained as the above-mentioned “winding deviation”, the step deviation was evaluated as follows.

[0572] exist Fig. 9A roll of a microporous membrane is placed on the inspection fixture shown, and the roll is dropped from a height of 300 mm onto the impact table to apply an impact to the roll. The roll to which the impact is applied is placed horizontally, and the distance from the lower surface of the roll to the upper surface of the roll is measured, and the offset width is calculated as follows. The longer the distance, the larger the step offset.

[0573] Offset width = (distance between the upper and lower surfaces of the winding body after step offset) - (winding body split width)

[0574] The evaluation criteria for step deviation are as follows.

[0575] (Evaluation criteria for curling)

[0576] A: 19cm or more

[0577] B: Less than 19cm and more than 15cm

[0578] C: less than 15cm

[0579] (Evaluation criteria for winding deviation)

[0580] A: Winding offset 0 roll / 10 rolls

[0581] B: Winding deviation is more than 1 roll and less than 2 rolls / 10 rolls

[0582] C: Winding deviation of more than 3 turns

[0583] (Evaluation criteria for step deviation)

[0584] A: 0mm or more and less than 1mm

[0585] B: 1mm or more and less than 10mm

[0586] C: 10mm or more

[0587] The measurement results and evaluation results of Examples and Comparative Examples are shown in the following table.

[0588] [Table 3-1]

[0589] Table 3. Separators

[0590]

[0591] [Table 3-2]

[0592] Table 3. Separators

[0593]

[0594] [Table 4]

[0595] Table 4. Separators

[0596]

[0597] Industrial Applicability

[0598] The electric storage device separator of the present application can be suitably used in various electric storage devices, and is preferably a lithium ion secondary battery.

[0599] Description of Reference Numerals

[0600] 1Inorganic filler

[0601] 2 Granular polymer

[0602] 10. Base material (as a base material of a polyolefin microporous membrane)

[0603] 20 Covering Layers

[0604] H is the maximum height of the granular polymer in the vertical direction relative to the separator surface

[0605] W is the maximum width of the granular polymer in the horizontal direction relative to the separator surface.

Claims

1. A separator for an electrical storage device, comprising a substrate and a covering layer, wherein the substrate is a polyolefin microporous membrane containing polyolefin as a main component, and the covering layer is disposed on at least one surface of the substrate. The covering layer comprises a particulate polymer of an inorganic filler and a thermoplastic polymer, The particulate polymer comprises particulate polymer protruding from the surface of the inorganic filler part, The static friction coefficient of the covering layer is greater than or equal to 0.40 and less than or equal to 0.

60.

2. The electrical storage device separator according to claim 1, wherein A portion of the surface of the protruding particulate polymer has defects.

3. The electrical storage device separator according to claim 1, wherein In the surface observation of the covering layer, the ratio of the area of ​​the particulate polymer falling-off portion to the total area of ​​the particulate polymer is 10% or less.

4. The electrical storage device separator according to claim 1, wherein The covering layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer. When the thickness of the inorganic filler portion is L1 and the maximum distance from the boundary line between the substrate and the covering layer to the outer surface of the inorganic filler formed in the inclined shape is L2, the average value of the inclination rate L2 / L1 of the covering layer is greater than 1.

2.

5. The electric storage device separator according to claim 1, wherein The covering layer is formed in an inclined shape so as to become thicker toward the protruding particulate polymer. When the thickness of the inorganic filler part is set to L1, the maximum distance from the boundary line of the substrate-covering layer to the outer surface of the inorganic filler formed in the inclined shape is set to L2, and the maximum distance from the boundary line of the substrate-covering layer to the outline of the protruding granular polymer is set to L3, the average value of the coverage rate of the protruding granular polymer (L2-L1) / (L3-L1) is greater than 0.

4.

6. The electrical storage device separator according to claim 1, wherein More than 20% of the protruding particulate polymer contacts the surface of the substrate.

7. The separator for an electrical storage device according to claim 1, wherein The cover layer has a 180° peel strength from the substrate of 200 gf / cm or more.

8. The electric storage device separator according to claim 1, wherein In the surface observation of the covering layer, the Voronoi segmentation is performed with the protruding granular polymer as the parent point, and the area of ​​the obtained Voronoi polygon (s i ) has a coefficient of variation (cv) of 0.10 or more and 0.60 or less.

9. The electric storage device separator according to claim 1, wherein The number of the protruding particulate polymers is 50% or more of the total number of the particulate polymers contained in the covering layer.

10. The electric storage device separator according to claim 1, wherein The particle size distribution of the granular polymer is 1.1 or less.

11. The electric storage device separator according to claim 1, wherein The particulate polymer is a primary particle.

12. The electric storage device separator according to claim 11, wherein The average particle diameter of the primary particles is 1 μm or more and 10 μm or less. 13 . The electrical storage device separator according to claim 1 , wherein the heat shrinkage rate in TD at 130° C. for 1 hour is 5% or less. 14 . The electrical storage device separator according to claim 1 , wherein the thermal shrinkage ratio in TD at 150° C. for 1 hour is 5% or less. 15 . An electrical storage device comprising the electrical storage device separator according to claim 1 .

Citation Information

Patent Citations

  • Separator for lithium secondary battery and a method of making the same

    KR1020160118979A

  • Layered body, separator, and non-aqueous secondary battery

    WO2016031466A1

  • Functional layer for electrochemical elements, separator with functional layer for electrochemical elements, and electrochemical element

    WO2020175079A1

  • Functional layer for electrochemical elements and method for producing same, separator with functional layer for electrochemical elements and method for producing same, and electrochemical element and method for producing same

    WO2021085144A1